Plastic ionic crystals, compositions containing same, methods for producing same and uses thereof

JP2024512192A5Inactive Publication Date: 2025-01-30HYDRO QUEBEC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023546268
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-08-30
Filing Date
2022-02-04
Publication Date
2025-01-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The conduction mechanisms and relationships between cations and anions in flexible ionic crystals are not well understood, making it difficult to predict whether they will form ionic melts or plastic crystals at specific temperatures, and existing solid electrolytes lack optimal performance.

Method used

Development of flexible ionic crystals comprising delocalized anions paired with guanidine, amidine, or phosphazene organic superbase-derived cations, which can be monocationic or multi-cationic, and incorporated into compositions with additional components such as polymers and inorganic particles to enhance conductivity.

Benefits of technology

The flexible ionic crystals exhibit improved conductivity and stability, making them suitable for use as solid electrolytes in electrochemical cells, supercapacitors, and batteries, addressing the limitations of traditional solid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present technology relates to plastic ionic crystals comprising at least one delocalized anion paired with at least one organic guanidine, amidine or phosphazene organic superbase derived cation for use in electrochemical applications, particularly in electrochemical storage batteries such as batteries, electrochromic devices and supercapacitors. The present technology also relates to plastic ionic crystal compositions, plastic ionic crystal-based solid electrolyte compositions, plastic ionic crystal-based solid electrolytes, electrode materials comprising plastic ionic crystals or plastic ionic crystal compositions. Their use in electrochemical cells and electrochemical storage batteries, as well as their preparation methods and NHO-stabilized intermediate ionic-neutral complexes are also described.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority under applicable law to U.S. Provisional Patent Application No. 63 / 146,356, filed February 5, 2021, and U.S. Provisional Patent Application No. 63 / 260,710, filed August 30, 2021, the entire contents of which are incorporated herein by reference for all purposes.

[0002] Technical Field The present application relates to the field of plastic ionic crystals and their use in electrochemical applications. More particularly, the present application relates to the field of plastic ionic crystals, compositions containing them, methods for their preparation, and their use as solid electrolytes in electrochemical cells, electrochromic devices, supercapacitors, electrochemical accumulators, in particular all-solid-state batteries. [Background technology]

[0003] background Plastic ionic crystals are considered promising materials for solid electrolytes. Although the technology is still in its infancy, plastic crystal-based ionic conductors exhibit significant advantages over conventional solid electrolyte materials, including high flexibility and plasticity, non-flammability, exceptional ionic conductivity, and good thermal and electrochemical properties.

[0004] Despite their great advantages, the conduction mechanisms and the relationships between the cations or anions and the physical properties of these materials are not well understood, so it is not trivial to predict which combinations of cations and anions are likely to form ionic melts or liquids or plastic crystals at a particular temperature.

[0005] Therefore, there is a need for the development of new solid electrolytes based on plastic ionic crystals that eliminate one or more of the disadvantages of, or provide one or more advantages over, conventional solid electrolytes. Summary of the Invention [Means for solving the problem]

[0006] overview According to a first aspect, the present technology relates to plastic ionic crystals comprising at least one delocalized anion paired with at least one guanidine, amidine or phosphazene organic superbase derived cation.

[0007] According to one embodiment, the plastic ionic crystal is a multicationic plastic ionic crystal comprising at least two delocalized anions paired with at least two guanidine, amidine or phosphazene organic superbase derived cations.

[0008] According to another embodiment, the delocalized anion is trifluoromethanesulfonate (or triflate) [TfO] - , Bis(trifluoromethanesulfonyl)imide [TFSI] - , bis(fluorosulfonyl)imide [FSI] - , 2-trifluoromethyl-4,5-dicyanoimidazolate [TDI] - , hexafluorophosphate [PF6] - and tetrafluoroborate [BF4] - According to one example, the delocalized anion is selected from the group consisting of [TFSI] - Another example is when the delocalized anion is [FSI] - It is.

[0009] According to another embodiment, the guanidine, amidine or phosphazene organic superbase is selected from the group consisting of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), 2-tert-butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-diazaphosphorine (BEMP), tert-butylimino-tri(pyrrolidino)phosphorane (BTPP) and tert-butylimino-tris(dimethylamino)phosphorane (P1-t-Bu).

[0010] According to another embodiment, the cation is a guanidine, amidine or phosphazene organic superbase derived cation of formulas 2-8: [ka] (In the formula, Plastic ion crystals are monocationic plastic ion crystals, R 1 is a hydrogen atom or C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-acrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate and carbonyloxy-C1-C 10 or a linear or branched substituent selected from alkyl-acrylate; Plastic ion crystals are multicationic plastic ion crystals, R 1 is an optionally substituted organic bridging group separating at least two of the cations, and is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10Alkylene, linear or branched polyether, linear or branched polyester, C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene and C3-C 12 heterocycloalkylene) is selected from the group consisting of:

[0011] In some embodiments, R 1 is a hydrogen atom, and the plastic ion crystal is a proton plastic ion crystal.

[0012] In some other embodiments, R 1 But, C1~C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-methacrylate and carbonylamino-C1-C 10 The straight or branched substituents are selected from alkyl-acrylates, and the plastic ionic crystals are crosslinked plastic ionic crystals.

[0013] According to some preferred embodiments, the plastic ionic crystal is a plastic ionic crystal of formulas 10-16: [ka] [ka] (In the formula, X - is [TfO] - , [TFSI] - , [FSI] - , [TDI] - , PF6 - and [BF4] - is a delocalized anion selected from the group consisting of: Plastic ion crystals are monocationic plastic ion crystals, R 1 is a hydrogen atom or C1-C 10 Alkyl-acrylate, C1-C10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-acrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate and carbonyloxy-C1-C 10 or a linear or branched substituent selected from alkyl-acrylate; Plastic ion crystals are multicationic plastic ion crystals, R 1 is an optionally substituted organic bridging group separating at least two of the cations, and is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene and C3-C 12 heterocycloalkylene) is selected from.

[0014] According to some preferred embodiments, the delocalized anion is [TFSI] - and [FSI] - Anions, preferably [FSI] - is selected from the group consisting of:

[0015] According to another aspect, the present technology relates to a plastic ionic crystal composition comprising at least one plastic ionic crystal as defined herein and at least one additional component and / or at least one polymer.

[0016] According to one embodiment, the additional component is selected from the group consisting of a solvent, an ion conductor, an inorganic particle, a glass particle, a ceramic particle, a plasticizer, and a combination of at least two thereof.

[0017] In some embodiments, the inorganic particles comprise compounds having a garnet, NASICON-type, LISICON-type, thio-LISICON-type, LIPON-type, perovskite-type, antiperovskite-type, or argyrodite-type structure, or MPS-type, MPSO-type, MPSX-type, MPSOX-type compounds (wherein M is an alkali metal or alkaline earth metal and X is F, Cl, Br, I, or a combination of at least two thereof) in a crystalline, amorphous, and / or glass-ceramic phase, or a mixture of at least two thereof.

[0018] In some preferred embodiments, the inorganic particles are in a crystalline phase, an amorphous phase, a glass-ceramic phase, or a combination thereof, of the following compounds: MLZO (e.g., M7La3Zr2O 12 , M (7-a) La3Zr2Al b O 12 , M (7-a) La3Zr2Ga b O 12 , M (7-a) La3Zr (2-b) Ta b O 12 and M. (7-a) La3Zr (2-b) Nb b O 12 );MLTaO (e.g., M7La3Ta2O 12 , M5La3Ta2O 12 and M6La3Ta 1.5 Y 0.5 O 12 );MLSnO (e.g., M7La3Sn2O 12 );MAGP(e.g., M 1+a Al a Ge 2-a (PO4)3); MATP (e.g., M 1+a Al a Ti 2-a(PO4)3);MLTiO (e.g., M 3a La (2 / 3-a) TiO3);MZP (e.g., M a Zr b (PO4) c );MCZP (e.g., M a Ca b Zr c (PO4) d );MGPS(e.g., M 10 GeP2S 12 M a Ge b P c S d );MGPSO(e.g., M a Ge b P c S d O e ); MSiPS (e.g., M 10 SiP2S 12 M a S b P c S d );MSiPSO (e.g., M a S b P c S d O e ); MSnPS (e.g., M 10 SnP2S 12 M a Sn b P c S d );MSnPSO (e.g., M a Sn b P c S d O e );MPS(e.g., M7P3S 11 M a P b S c );MPSO (e.g., M a P b S c O d );MZPS(e.g., M a Zinc b P c S d );MZPSO(e.g., M a Zinc b Pc S d O e );xM2S-yP2S5;xM2S-yP2S5-zMX;xM2S-yP2S5-zP2O5;xM2S-yP2S5-zP2O5-wMX;xM2S-yM2O-zP2S5;xM2S- yM2O-zP2S5-wMX;xM2S-yM2O-zP2S5-wP2O5;xM2S-yM2O-zP2S5-wP2O5-vMX;xM2S-ySiS2;MPSX (for example, M7P3S 11 X, M7P2S8X and M6PS5X a P b S c X d );MPSOX(For example, M a P b S c O d X e );MGPSX(For example, M a Ge b P c S d X e );MGPSOX(For example, M a Ge b P c S d O e X f );MSiPSX(e.g., M a S b P c S d X e );MSiPSOX(e.g., M a S b P c S d O e X f );MSnPSX (e.g., M a Sn b P c S d X e );MSnPSOX (e.g., M a Sn b P c S d O e X f );MZPSX(For example, M a Zinc b P c S dX e );MZPSOX(For example, M a Zinc b P c S d O e X f );M3OX;M2HOX;M3PO4;M3PS4;and M a PO b N c (a=2b+3c-5) (In the formula, M is an alkali metal ion, an alkaline earth metal ion, or a combination thereof, and when M comprises an alkaline earth metal ion, the number of M's is adjusted to achieve electroneutrality; X is selected from F, Cl, Br, I, or combinations thereof; a, b, c, d, e and f are numbers other than 0 and are independently selected in each formula to achieve electroneutrality; v, w, x, y and z are numbers other than 0 and are independently selected in each formula to provide a stable compound. Includes at least one of the following.

[0019] In some other embodiments, the inorganic particles are ceramics or glass-ceramics. According to one example, the ceramics or glass-ceramics are oxide-based ceramics, sulfide-based ceramics, oxysulfide-based ceramics, or a combination of at least two of these. For example, the sulfide-based ceramics are Li 10 GeP2S 12 , Li6PS5Cl, Li2S-P2S5, Li7P3S 11 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li 9.6 P3S 12 and Li 3.25 P 0.95 S4. According to a variant of the invention, the sulfide-based ceramic is Li6PS5Cl.

[0020] In some other embodiments, the ceramic or glass-ceramic is present in the plastic ionic crystal composition at a concentration of at least 50% by weight. For example, the ceramic or glass-ceramic is present in the plastic ionic crystal composition at a concentration of about 50% to about 95% by weight, or about 55% to about 95% by weight, or about 60% to about 95% by weight, or about 65% to about 95% by weight, or about 70% to about 95% by weight, or about 75% to about 95% by weight, or about 80% to about 95% by weight, or about 85% to about 95% by weight, or about 90% to about 95% by weight, including the upper and lower limits. According to a variant of interest, the ceramic or glass-ceramic is present in the plastic ionic crystal composition at a concentration of about 90% by weight. According to another variant of interest, the plastic crystal is present in the plastic ionic crystal composition at a concentration of about 10% by weight.

[0021] In some other preferred embodiments, the inorganic particles are filler additives selected from the group consisting of titanium dioxide (TiO2), alumina (Al2O3), and silicon dioxide (SiO2) particles or nanoparticles.

[0022] In some embodiments, the polymer is linear or branched.

[0023] In some embodiments, the polymer is crosslinked.

[0024] In some embodiments, the polymer is present in the plastic ionic crystal composition at a concentration of at least 10% by weight. For example, the polymer is present in the plastic ionic crystal composition at a concentration of about 5% to about 45% by weight, or about 10% to about 45% by weight, or about 15% to about 45% by weight, or about 20% to about 45% by weight, or about 25% to about 45% by weight, or about 30% to about 45% by weight, or about 35% to about 45% by weight, or about 40% to about 45% by weight, inclusive.

[0025] In some preferred embodiments, the polymer is a polyether-type polymer, for example, the polyether-type polymer is a polyethylene oxide (PEO)-based polymer.

[0026] In some other preferred embodiments, the polymer is a block copolymer comprised of at least one lithium ion solvating segment and optionally at least one crosslinkable segment, wherein the lithium ion solvating segment comprises a repeating unit of formula 32: [ka] (In the formula, R 3 is a hydrogen atom, C1-C 10 Alkyl group or -(CH2-OR 4 R 5 ) group; R 4 is (CH2-CH2-O) m and; R 5 is a hydrogen atom and C1-C 10 alkyl groups; y is an integer selected from the range of 10 to 200,000; m is an integer selected from the range of 0 to 10. The copolymer is selected from homopolymers or copolymers having the formula:

[0027] In some preferred embodiments, the crosslinkable segments of the copolymer are polymer segments that contain at least one functional group that is multi-dimensionally crosslinkable by irradiation or heat treatment.

[0028] According to another embodiment, the plastic ionic crystal composition is a plastic ionic crystal-based electrolyte composition.

[0029] According to another aspect, the present technology relates to a binder comprising the plastic ionic crystalline composition defined herein.

[0030] According to another aspect, the present technology relates to an electrochemical cell comprising a plastic ionic crystal composition as defined herein.

[0031] According to another aspect, the present technology relates to a supercapacitor comprising a plastic ionic crystal composition as defined herein.

[0032] According to one embodiment, the supercapacitor is a carbon-carbon supercapacitor.

[0033] According to another aspect, the present technology relates to an electrochromic material comprising a plastic ionic crystal composition as defined herein.

[0034] According to another aspect, the present technology relates to a solid electrolyte composition comprising a plastic ionic crystal as defined herein or a plastic ionic crystal composition as defined herein and at least one salt or at least one additional component.

[0035] In some embodiments, the salt is an ionic salt. For example, the ionic salt is selected from lithium salt, sodium salt, potassium salt, calcium salt and magnesium salt, and preferably, the ionic salt is a lithium salt. According to a variant of the object, the lithium salt is selected from lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide) (Li(FSI)(TFSI)), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium difluorophosphate (LiDFP), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (Li BOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiOTf), lithium fluoroalkylphosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(C6O2)2] (LiBBB), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiFOB), with the formula LiBF2O4R x (In the formula, R x =C 2~4 alkyl), and combinations of at least two thereof.

[0036] In some embodiments, the additional component is selected from the group consisting of ion-conducting materials, inorganic particles, glass particles, ceramic particles, plasticizers, other similar components, and combinations of at least two of these. For example, the ceramic particles are nanoceramics. According to a variant of interest, the additional component is selected from NASICON-type, LISICON-type, thio-LiSICON-type compounds in crystalline and / or amorphous form, garnets, and combinations of at least two of these.

[0037] According to another aspect, the present technology relates to a solid electrolyte comprising a solid electrolyte composition as defined herein, the solid electrolyte being optionally crosslinked.

[0038] According to another aspect, the present technology relates to a solid electrolyte comprising plastic ionic crystals as defined herein, the solid electrolyte being optionally crosslinked.

[0039] According to another aspect, the present technology relates to an electrode material comprising an electrochemically active material and a plastic ionic crystal composition as defined herein, wherein the plastic ionic crystal composition is optionally crosslinked.

[0040] According to another aspect, the present technology relates to an electrode material comprising an electrochemically active material and plastic ionic crystals as defined herein, where the plastic ionic crystals are optionally crosslinked.

[0041] According to one embodiment, the plastic ionic crystal or plastic ionic crystal composition is the binder.

[0042] In some embodiments, the electrochemically active material is in the form of particles.

[0043] In some embodiments, the electrochemically active material is selected from the group consisting of metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanate, metal fluorophosphates, lithium metal fluorophosphates, metal oxyfluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, lithium metal sulfates, metal halides (e.g., metal fluorides), lithium metal halides (e.g., lithium metal fluorides), sulfur, selenium, and combinations of at least two thereof. For example, the metal of the electrochemically active material is selected from the group consisting of titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), zirconium (Zr), zinc (Zn), niobium (Nb), and combinations of at least two thereof.

[0044] In some embodiments, the electrode material further comprises at least one conductive material. For example, the conductive material is selected from carbon black, acetylene black, graphite, graphene, carbon fiber, carbon nanofiber, carbon nanotube, and a combination of at least two of them. According to a variant of the object, the conductive material is acetylene black.

[0045] In some embodiments, the electrode material has an electrochemically active material:plastic ion crystallinity ratio of less than about 6, or less than about 5, or less than about 4, or less than about 3, preferably less than about 4.

[0046] In some embodiments, the electrode material has a porosity of less than about 8%, or less than about 7%, or less than about 6%, or less than about 5%, or less than about 4%, or less than about 3%, or less than about 2%, or less than about 1%, preferably less than about 5%.

[0047] According to another aspect, the present technology relates to an electrode comprising an electrode material as defined herein on a current collector.

[0048] According to another aspect, the present technology relates to an electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein at least one of the negative electrode, the positive electrode and the electrolyte comprises at least one plastic ionic crystal as defined herein, and the plastic ionic crystal is optionally crosslinked.

[0049] According to another aspect, the present technology relates to an electrochemical cell comprising a negative electrode, a positive electrode, and an electrolyte, wherein at least one of the negative electrode, the positive electrode, and the electrolyte comprises a plastic ionic crystal composition as defined herein, and wherein the plastic ionic crystal composition is optionally crosslinked.

[0050] According to another aspect, the present technology relates to an electrochemical cell including a negative electrode, a positive electrode, and an electrolyte, wherein at least one of the negative electrode and the positive electrode is as defined herein.

[0051] According to another aspect, the present technology relates to an electrochemical cell comprising an anode, a cathode and a solid electrolyte as defined herein.

[0052] According to another aspect, the present technology relates to an electrochemical storage battery comprising at least one electrochemical cell as defined herein.

[0053] According to one embodiment, the electrochemical accumulator is a battery chosen from lithium batteries, lithium ion batteries, sodium batteries, sodium ion batteries, magnesium batteries and magnesium ion batteries. According to a variant of the subject, the battery is a lithium battery or a lithium ion battery.

[0054] According to another aspect, the present technology provides a method for preparing a plastic ionic crystal as defined herein or a plastic ionic crystal composition as defined herein, comprising the steps of: (i) reacting at least one guanidine, amidine or phosphazene organic superbase with at least one proton source to form at least one complex comprising a protonated guanidine, amidine or phosphazene organic superbase-derived cation and a counterion; and (ii) reacting a complex comprising a cation and a counterion derived from a protonated guanidine, amidine or phosphazene organic superbase with at least one ionic salt; The present invention relates to a method comprising the steps of:

[0055] According to one embodiment, the guanidine, amidine or phosphazene organic superbase is selected from the group consisting of DBU, DBN, MTBD, BEMP, BTPP and P1-t-Bu. According to a variant of interest, the guanidine, amidine or phosphazene organic superbase is BEMP. According to another variant of interest, the guanidine, amidine or phosphazene organic superbase is DBU.

[0056] According to another embodiment, the ionic salt is [TfO] - , [TFSI] - , [FSI] - , [TDI] - , PF6 - and [BF4] - According to a variant of the invention, the delocalized anion is selected from the group consisting of [TFSI] - According to another variant of the invention, the delocalized anion is [FSI] - It is.

[0057] According to another embodiment, the ionic salt is an alkali or alkaline earth metal salt, for example the alkali or alkaline earth metal salt is a lithium salt, a sodium salt, a potassium salt, a calcium salt or a magnesium salt, preferably a lithium salt.

[0058] According to another embodiment, steps (i) and (ii) are performed sequentially, simultaneously or partially overlapping with one another in time, for example, steps (i) and (ii) are performed sequentially, where reacting the guanidine, amidine or phosphazene organic superbase with a proton source is performed before reacting a complex comprising a cation and counterion derived from the protonated guanidine, amidine or phosphazene organic superbase with an ionic salt.

[0059] In another embodiment, a guanidine, amidine or phosphazene organic superbase, a proton source and an ionic salt are mixed together and allowed to react.

[0060] According to another embodiment, steps (i) and (ii) are carried out in the presence of a solvent.For example, the solvent is selected from the group consisting of dichloromethane, dimethyl carbonate, acetonitrile, ethanol and miscible combinations of at least two of them.According to another variant of the object, the solvent is acetonitrile.

[0061] In some embodiments, the solvent is the proton source in step (i).

[0062] According to another embodiment, the proton source of step (i) is a first proton source, and steps (i) and (ii) are carried out in the presence of a second proton source. For example, the second proton source is an acid selected from the group consisting of carboxylic acids (e.g., formic acid, acetic acid, propionic acid, lactic acid and trifluoroacetic acid), p-toluenesulfonic acid, sulfuric acid, hydroiodic acid, hydrobromic acid, hydrochloric acid, nitric acid and hydrofluoric acid.

[0063] According to another embodiment, steps (i) and (ii) are carried out in the presence of an activator and / or stabilizer, and the method further comprises the step of forming a stabilized intermediate ion-neutral complex.

[0064] In some embodiments, the activator and / or stabilizer is a bis-silylated compound of formula 17: [ka] (In the formula, Z is a straight or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 a substituted or unsubstituted organic group selected from alkylene, linear or branched polyethers, linear or branched polycarbonates, linear or branched polythiocarbonates, linear or branched polyamides, linear or branched polyimides, linear or branched polyurethanes, linear or branched polysiloxanes, linear or branched thioethers, linear or branched polyphosphazenes, linear or branched polyesters, and linear or branched polythioesters; R 2 is independently, at each occurrence, selected from the group consisting of alkyl groups, aryl groups, and arylalkyl groups. It is.

[0065] According to another embodiment, the method further comprises the step of preparing a bis-silylated compound of formula 17.

[0066] In some embodiments, the step of preparing a bis-silylated compound of formula 17 is carried out by a silylation reaction of a compound containing at least two hydroxyl groups with a silylation reagent. For example, the compound containing at least two hydroxyl groups is selected from the group consisting of glycerol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol, 1,2-butanediol, 2,3-butanediol, 1,3-butanediol, 1,2-pentanediol, ethohexadiol, p-menthane-3,8-diol, 2-methyl-2,4-pentanediol, polycaprolactone diol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, polyethylene glycol, 2,2,3,3,4,4,5,5-octafluoro-1,6-hexanediol, and combinations of at least two of these. According to a variant of interest, the bis-silylated compound of formula 17 is a bis-silylated diethylene glycol. According to another variant of the object, the bis-silylated compound of formula 17 is a bis-silylated glycerol.

[0067] In some embodiments, the silylation reaction is carried out by a base-catalyzed silylation reaction, in which the acidic or active hydrogen on the hydroxyl group (R 2 )3Si-groups.

[0068] In some embodiments, the silylation reaction is carried out in the presence of a base. According to one variant of interest, the base is 4-dimethylaminopyridine. According to another variant of interest, the base is imidazole.

[0069] In some embodiments, the silylation reaction is carried out in the presence of an aprotic solvent. According to one variant of interest, the aprotic solvent is dichloromethane. According to another variant of interest, the aprotic solvent is tetrahydrofuran.

[0070] In some embodiments, the silylation reagent is selected from the group consisting of trialkylsilyl chlorides, trimethylsilyl chloride (TMS-Cl), triethylsilyl chloride (TES-Cl), isopropyldimethylsilyl chloride (IPDMS-Cl), diethylisopropylsilyl chloride (DEIPS-Cl), tert-butyldimethylsilyl chloride (TBDMS-Cl or TBS-Cl), tert-butyldiphenylsilyl chloride (TBDPS-Cl or TPS-Cl), and triisopropylsilyl chloride (TI The silylating agent is selected from the group consisting of PS-Cl), nitrogen-containing silyl ethers, N,O-bis(tert-butyldimethylsilyl)acetamide (BSA), N-methyl-N-(trimethylsilyl)trifluoroacetamide (MSTFA), N-(trimethylsilyl)dimethylamine (TMSDEA), N-(trimethylsilyl)imidazole (TMSI or TSIM), N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA), and N-methyl-N-(trimethylsilyl)acetamide (MSA). According to a variant of interest, the silylating agent is trimethylsilyl chloride (TMS-Cl). According to another variant of interest, the silylating agent is tert-butyldimethylsilyl chloride (TBDMS-Cl or TBS-Cl).

[0071] In some embodiments, the silylation reagent is added in a molar ratio of about 1:0.9 "-OH groups to be derivatized:silyl groups."

[0072] In some other embodiments, the silylation reagent is added in a molar ratio of about 1:1 "-OH groups to be derivatized:silyl groups."

[0073] In some other embodiments, the silylation reagent is added in excess relative to the number of hydroxyl groups on the compound containing at least two hydroxyl groups. According to one example, the amount of silylation reagent is in the range of about 2 equivalents to about 5 equivalents per equivalent of the compound containing at least two hydroxyl groups, inclusive. For example, the amount of silylation reagent is in the range of about 2 equivalents to about 4.5 equivalents, or about 2 equivalents to about 4 equivalents, or about 2 equivalents to about 3.75 equivalents, or about 2 equivalents to about 3.5 equivalents per equivalent of the compound containing at least two hydroxyl groups, inclusive.

[0074] In some embodiments, the silylation reaction is carried out at room temperature.

[0075] In some embodiments, steps (i) and (ii) are carried out at a temperature in the range of about 20° C. to about 200° C. (inclusive). For example, steps (i) and (ii) are carried out at a temperature in the range of about 40° C. to about 80° C., or about 45° C. to about 75° C., or about 50° C. to about 70° C., or about 55° C. to about 65° C. (inclusive).

[0076] In some embodiments, steps (i) and (ii) are carried out for at least 4 days.

[0077] According to another embodiment, the method further comprises a purification step, for example by extraction, distillation or evaporation.

[0078] According to another embodiment, the method further comprises a functionalization step. According to one example, the functionalization step is carried out by reaction between the -NH functional group of the protonated guanidine, amidine or phosphazene organic superbase-derived cation and at least one precursor of a crosslinkable functional group. For example, the crosslinkable functional group may be any of C1 to C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate, carbonyloxy-C1~C 10 Alkyl-acrylate, carbonylamino-C1~C10 Alkyl-methacrylate, and carbonylamino-C1-C 10 The alkyl-acrylate group is selected from the group consisting of:

[0079] According to another embodiment, the method further comprises a step of coating the plastic ion crystal composition or the suspension containing the plastic ion crystal on a substrate.For example, the coating step is carried out by at least one of doctor blade coating, comma coating, reverse comma coating, printing such as gravure coating, or slot die coating.According to an objective variant, the coating step is carried out by at least one of doctor blade coating or slot die coating.

[0080] According to another embodiment, the method further comprises the step of drying the composition or suspension. According to one example, the drying and coating steps are performed simultaneously.

[0081] According to another embodiment, the method further comprises a crosslinking step. According to one example, the crosslinking step is carried out by UV irradiation, by heat treatment, by microwave irradiation, under electron beam, by gamma irradiation, or by X-ray irradiation. According to a variant of the object, the crosslinking step is carried out by UV irradiation, heat treatment, or under electron beam. In some embodiments, the crosslinking step is carried out in the presence of a crosslinking agent, a thermal initiator, a photoinitiator, a catalyst, a plasticizer, or a combination of at least two of these. According to a variant of the object, the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone (Irgacure™ 651).

[0082] According to another aspect, the present technology provides a method for the preparation of a bis-silylated compound of formula 17, comprising reacting at least one guanidine, amidine or phosphazene organic superbase derived cation with at least one bis-silylated compound of formula 17: [ka] (In the formula, Z is a straight or branched C1-C10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 a substituted or unsubstituted organic group selected from alkylene, linear or branched polyethers, linear or branched polycarbonates, linear or branched polythiocarbonates, linear or branched polyamides, linear or branched polyimides, linear or branched polyurethanes, linear or branched polysiloxanes, linear or branched thioethers, linear or branched polyphosphazenes, linear or branched polyesters, and linear or branched polythioesters; R 2 is independently, at each occurrence, selected from the group consisting of alkyl groups, aryl groups, and arylalkyl groups. This invention relates to a stabilized intermediate ion-neutral complex obtained by reacting

[0083] According to one embodiment, the cation derived from a guanidine, amidine or phosphazene organic superbase is protonated 1,8-diazabicyclo[5.4.0]undec-7-ene [H-DBU] + , protonated 1,5-diazabicyclo[4.3.0]non-5-ene [H-DBN] + , protonated 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene [H-MTBD] + , protonated 2-tert-butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-diazaphosphorine [H-BEMP] + , protonated tert-butylimino-tri(pyrrolidino)phosphorane [H-BTPP] + , and protonated tert-butylimino-tris(dimethylamino)phosphorane [P1-t-Bu] + is selected from the group consisting of: In some embodiments, the stabilized intermediate ion-neutral complex is represented by Formulas 25-31: [ka] (In the formula, Z and R 2 is as defined herein; X - is [TfO] - , [TFSI] - , [FSI] - , [TDI] - , PF6 - and [BF4] - is a delocalized anion selected from the group consisting of It is of the following.

[0084] According to another aspect, the present technology provides a method for preparing a plastic ionic crystal as defined herein or a plastic ionic crystal composition as defined herein, comprising the steps of: (i) reacting a guanidine, amidine or phosphazene organic superbase with an organic bridging compound to form a multicationic complex comprising at least two organic superbase cationic moieties separated by an optionally substituted organic bridging group and paired with a counterion; and (ii) reacting the multicationic complex with at least one ionic salt; The present invention relates to a method comprising the steps of:

[0085] According to one embodiment, the guanidine, amidine or phosphazene organic superbase is selected from the group consisting of DBU, DBN, MTBD, BEMP, BTPP and P1-t-Bu. According to a variant of interest, the guanidine, amidine or phosphazene organic superbase is BEMP. According to another variant of interest, the guanidine, amidine or phosphazene organic superbase is DBU.

[0086] According to another embodiment, the organic bridging compound comprises an optionally substituted organic bridging group and at least two anionic leaving groups. For example, the anionic leaving groups are halides. According to a variant of interest, the halide is F - , Cl - , Br - and I -According to another variant of the invention, the halide is selected from Br - It is.

[0087] According to another embodiment, the optionally substituted organic bridging group is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene, and C3-C 12 heterocycloalkylene.

[0088] In some embodiments, the organic bridging group is 1,2,4,5-tetrakis(bromomethyl)benzene.

[0089] According to another embodiment, the ionic salt is [TfO] - , [TFSI] - , [FSI] - , [TDI] - , PF6 - and [BF4] - According to a variant of the invention, the delocalized anion is selected from the group consisting of [TFSI] - According to another variant of the invention, the delocalized anion is [FSI] - It is.

[0090] According to another embodiment, the ionic salt is an alkali or alkaline earth metal salt. For example, the alkali or alkaline earth metal salt is a lithium salt, a sodium salt, a potassium salt, a calcium salt, or a magnesium salt. Preferably, the alkali or alkaline earth metal salt is a lithium salt.

[0091] According to another embodiment, steps (i) and (ii) are performed sequentially, simultaneously or partially overlapping with one another in time. According to one example, steps (i) and (ii) are performed sequentially, with the step of reacting the guanidine, amidine or phosphazene organic superbase with the organic bridging compound being performed before the step of reacting the multicationic complex with the ionic salt.

[0092] In another embodiment, a guanidine, amidine or phosphazene organic superbase, an organic crosslinking compound, and an ionic salt are mixed together and allowed to react.

[0093] According to another embodiment, steps (i) and (ii) are carried out in the presence of a solvent.For example, the solvent is selected from the group consisting of dichloromethane, dimethyl carbonate, acetonitrile, ethanol, and miscible combinations of at least two of these.According to an embodiment, the solvent is dichloromethane.

[0094] According to another embodiment, the step of reacting the guanidine, amidine or phosphazene organic superbase with the organic bridging compound is carried out in the presence of a base. According to a variant of interest, the base is triethylamine (Et3N).

[0095] In some embodiments, steps (i) and (ii) are performed at room temperature.

[0096] In some embodiments, the step of reacting the guanidine, amidine, or phosphazene organic superbase with the organic cross-linking compound is carried out for about 4 days.

[0097] In some embodiments, the step of reacting the multicationic complex with the ionic salt is carried out for about 3 days.

[0098] According to another embodiment, the method further comprises a purification step, for example by extraction, distillation or evaporation.

[0099] According to another embodiment, the method further comprises a step of coating the plastic ion crystal composition or the suspension containing the plastic ion crystal on a substrate.For example, the coating step is carried out by at least one of doctor blade coating, comma coating, reverse comma coating, printing such as gravure coating, or slot die coating.According to an objective variant, the coating step is carried out by at least one of doctor blade coating or slot die coating.

[0100] According to another embodiment, the method further comprises the step of drying the composition or suspension.

[0101] In some embodiments, the drying and coating steps are performed simultaneously. According to another aspect, the present technology provides a method for producing an electrode material as defined herein, comprising the steps of: (i) preparing a carbon and binder slurry; (ii) preparing a plastic ionic crystal-based catholyte; and (iii) preparing a plastic ionic crystal, carbon, and binder slurry; The present invention relates to a method comprising the steps of:

[0102] According to one embodiment, the step of preparing the carbon and binder slurry includes dispersing carbon in a binder composition.

[0103] According to another embodiment, the method further comprises the step of preparing a binder composition.

[0104] In some embodiments, the carbon comprises carbon black.

[0105] In some embodiments, the carbon comprises vapor grown carbon fibers.

[0106] According to another embodiment, the binder composition comprises a binder and, optionally, a solvent and / or a carbon dispersant.

[0107] In some embodiments, the binder comprises a fluorine-containing polymer.For example, the fluorine-containing polymer is polytetrafluoroethylene, polyvinylidene fluoride, or poly(vinylidene fluoride-co-hexafluoropropylene).According to a variant of interest, the fluorine-containing polymer is polyvinylidene fluoride.

[0108] In some embodiments, the solvent is N-methyl-2-pyrrolidone.

[0109] In some embodiments, the carbon dispersant is polyvinylpyrrolidone.

[0110] According to another embodiment, the step of preparing the binder composition is performed by mixing the binder with the solvent and / or the carbon dispersant, for example, by roll milling.

[0111] According to another embodiment, the step of preparing the plastic ionic crystal catholyte comprises diluting the plastic ionic crystals and an ionic salt in a solvent, for example, the solvent is N-methyl-2-pyrrolidone.

[0112] According to another embodiment, the step of preparing the plastic ionic crystal, carbon, and binder slurry comprises the stepwise addition of a plastic ionic crystal based catholyte to the carbon and binder slurry.

[0113] According to another embodiment, the method further comprises adding an electrochemically active material to the plastic ionic crystal, carbon, and binder slurry. For example, the electrochemically active material is lithium nickel manganese cobalt oxide (NMC).

[0114] According to another embodiment, the method further comprises coating the plastic ionic crystal, carbon and binder slurry on a current collector to obtain a plastic ionic crystal, carbon and binder electrode film on the current collector. For example, the coating step is performed by at least one of a doctor blade coating method, a comma coating method, a reverse comma coating method, a printing method such as gravure coating, or a slot die coating method. According to a variant of the object, the coating step is performed by a doctor blade coating method.

[0115] According to another embodiment, the method further comprises drying the plastic ionic crystals, the binder, and the carbon electrode film.

[0116] According to another embodiment, the method further comprises a step of calendering the plastic ionic crystal, the binder, and the carbon electrode film. For example, the calendering step is performed by a roll press method. [Brief description of the drawings]

[0117] [Figure 1] FIG. 1 is a flow diagram of a method for producing an electrode material according to one embodiment.

[0118] [Diagram 2] FIG. 2 is a flow diagram of a method for producing an electrode material according to one embodiment.

[0119] [Diagram 3] FIG. 3 is a proton nuclear magnetic resonance ( 1 H NMR) spectrum obtained for 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), as described in Example 1(b).

[0120] [Figure 4] FIG. 4 is a carbon-13 nuclear magnetic resonance ( 13 C NMR) spectrum obtained for plastic crystal 1, as described in Example 1(b).

[0121] [Diagram 5] FIG. 5 is a fluorine-19 nuclear magnetic resonance (F NMR) spectrum obtained for plastic crystal 1, as described in Example 1(b).

[0122] [Figure 6] FIG. 6 is a Lithium-7 Nuclear Magnetic Resonance (7Li NMR) spectrum obtained for plastic crystal 1, as described in Example 1(b).

[0123] [Figure 7] FIG. 7 shows mass spectra obtained by high performance liquid chromatography time-of-flight mass spectrometry (HPLC TOF-MS) using an electrospray ionization (ESI) source in (A) negative mode (ESI-) and (B) positive mode (ESI+), respectively, for plastic crystal 1, as described in Example 1(b).

[0124] [Figure 8] FIG. 8 shows the results of differential scanning calorimetry analysis obtained on plastic crystal 1, as described in Example 1(b).

[0125] [Figure 9] FIG. 9 shows mass spectra obtained by HPLC TOF-MS using an ESI ionization source in (A) positive mode (ESI+) and (B) negative mode (ESI-), respectively, for plastic crystal 11, as described in Example 1(b).

[0126] [Figure 10] FIG. 10 shows the results of a differential scanning calorimetry analysis obtained on plastic crystals 11, as described in Example 1(b).

[0127] [Figure 11] FIG. 11 is a 1H NMR spectrum obtained for plastic crystals 15 after post-functionalization, as described in Example 1(d).

[0128] [Figure 12] FIG. 12 shows the results of differential scanning calorimetry analysis obtained on plastic crystals 15 after post-functionalization, as described in Example 1(d).

[0129] [Figure 13] FIG. 13 shows the results of thermogravimetric analysis obtained on plastic crystals 15 after post-functionalization, as described in Example 1(d).

[0130] [Figure 14] FIG. 14 shows the results of differential scanning calorimetry analysis obtained on plastic crystals 16 after post-functionalization, as described in Example 1(d).

[0131] [Figure 15] FIG. 15 is a graph showing ionic conductivity results (S.cm−1) as a function of temperature (1000 / T, K−1) for the cell described in Example 1(e).

[0132] [Figure 16] FIG. 16 is a graph showing ionic conductivity results as a function of temperature for the cell described in Example 1(e).

[0133] [Figure 17] FIG. 17 is a graph showing ionic conductivity results as a function of temperature for cells 1 (●), 2 (■), 3 (▼), 4 (★), and 5 (▲), as described in Example 2.

[0134] [Figure 18] Figure 18 is a graph showing ionic conductivity results as a function of temperature for cells 6 (●), 7 (▲), 8 (×), 9 (■), 10 (◆, solid line), and 11 (◆, dotted line) as described in Example 2.

[0135] [Figure 19]FIG. 19 shows in (A) the atom numbering for the protonated DBU and bis-silylated derivative of diethylene glycol prepared in Example 1(a), and in (B) and (C) the 1H NMR and 13C NMR spectra, respectively, obtained for the stabilized intermediate ion-neutral complex described in Example 5.

[0136] [Figure 20] Figure 20 shows, in (A) and (B), respectively, 1H and 13C NMR spectra obtained for the stabilized intermediate ion-neutral complex over a 3-week period, as described in Example 5. Results were obtained at the start of the experiment (blue), after 2 days (red), 3 days (green), 9 days (purple), and 21 days (yellow).

[0137] [Figure 21] 21 shows 1H NMR spectra obtained over a 3 week period for the stabilized intermediate ion-neutral complex, recorded between 3.99 ppm and 4.30 ppm for (A) and between 6 ppm and 10.4 ppm for (B), as described in Example 5. Results were obtained at the start of the experiment (blue), after 2 days (red), 3 days (green), 9 days (purple), and 21 days (yellow).

[0138] [Figure 22] FIG. 22 shows mass spectra obtained by HPLC TOF-MS using an ESI ionization source in (A) positive mode (ESI+) and (B) negative mode (ESI-), respectively, for plastic crystal 30, as described in Example 6(b).

[0139] [Diagram 23] FIG. 23 shows the results of a differential scanning calorimetry analysis obtained on plastic crystals 30, as described in Example 6(b).

[0140] [Figure 24]FIG. 24 is a 1H NMR spectrum obtained for the tetracationic plastic ion crystal described in Example 7(b).

[0141] [Diagram 25] FIG. 25 is a 19F NMR spectrum obtained for the tetracationic plastic ion crystal described in Example 7(b).

[0142] [Figure 26] FIG. 26 is a graph of relaxation times as a function of temperature obtained for tetracationic plastic ion crystals, as described in Example 7(b).

[0143] [Figure 27] FIG. 27 shows a scanning electron microscope (SEM) image obtained for electrode 1, as described in Example 8(a).

[0144] [Figure 28] FIG. 28 shows a photograph of (A) the surface of a plastic crystalline positive electrode obtained by a conventional mixing method and (B) the surface of electrode 5 as described in Example 8(b).

[0145] [Figure 29] FIG. 29 is a graph of discharge capacity (mAh / g) as a function of cycle number for Cell 12, as described in Example 8(c).

[0146] [Diagram 30] FIG. 30 is a graph of current density and potential as a function of time for Cell 13, as described in Example 9.

[0147] [Diagram 31] FIG. 31 is a graph of current density and potential as a function of time for Cell 14, as described in Example 9.

[0148] [Diagram 32]FIG. 32 is a graph of current density and potential as a function of time for Cells 15 and 16, as described in Example 9.

[0149] [Diagram 33] FIG. 33 shows an Arrhenius plot of the log of the diffusion coefficient (D) versus 1 / kBT showing the temperature dependence of the diffusion rates of CH2 (▲), NH (×), FSI (◆), TFSI (●), LATP (Δ), and Li+ (■), as described in Example 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0150] Detailed Description The following detailed description and examples are for illustrative purposes only and should not be interpreted as further limiting the scope of the present invention. Rather, they are intended to cover all alternatives, modifications and equivalents that may be included as defined by this specification. The objectives, advantages and other features of the present plastic ionic crystal, plastic ionic crystal-based solid electrolyte composition, plastic ionic crystal-based solid electrolyte and electrode material containing said plastic ionic crystal, their preparation methods and uses will become more apparent and be better understood upon reading the following non-limiting description and reference made to the accompanying drawings.

[0151] Where applicable, process flow diagrams may be used to describe embodiments, but the present invention is not limited to those diagrams or the corresponding descriptions. Moreover, for the sake of brevity and clarity, not all diagrams include all steps, reactants and / or products, particularly so as not to overload the diagrams with steps, reactants and / or products. Some steps, reactants and / or products may be found in a single diagram, and the steps, reactants and / or products of the present disclosure shown in other diagrams may be easily inferred therefrom.

[0152] All technical and scientific terms and expressions used herein have the same definitions as those commonly understood by those skilled in the art when they relate to the present technology. Nevertheless, the definitions of some terms and expressions used herein are provided below.

[0153] When the term "about" is used herein, it means approximately in the region of or around. For example, when the term "about" is used in reference to a numerical value, it modifies the numerical value above and below by a variation of 10% from its nominal value. This term can also take into account, for example, experimental error or rounding of a measuring device.

[0154] When a range of values ​​is referred to in this application, the lower and upper limits of the range are always included in the definition, unless otherwise indicated. When a range of values ​​is referred to in this application, all intermediate ranges and subranges, as well as individual values ​​that fall within the range of values, are included in the definition.

[0155] When the article "a" is used to introduce an element in this application, it does not have the meaning of "only one," but rather "one or more." Of course, if the description states that a particular step, component, element, or feature "may" be included, it does not require that the particular step, component, element, or feature be included in every embodiment.

[0156] The chemical structures described herein are drawn according to conventions in the art, and when a drawn atom, such as a carbon atom, appears to contain incomplete valences, the valences are assumed to be satisfied by one or more hydrogen atoms, even if not explicitly drawn.

[0157] The term "alkyl" as used herein refers to a saturated hydrocarbon having between 1 and 10 carbon atoms, including straight-chain or branched alkyl groups. Non-limiting examples of alkyl groups may include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, isopropyl, tert-butyl, sec-butyl, isobutyl, and the like. When an alkyl group is located between two functional groups, the term alkyl also includes alkylene groups such as methylene, ethylene, propylene, and the like. "C m ~C n Alkyl" and "C m ~C n The term "alkylene" refers to an alkyl or alkylene group having, respectively, a designated number "m" to a designated number "n" of carbon atoms.

[0158] The term "cycloalkyl" or "cycloalkylene" as used herein refers to a group containing one or more saturated or partially unsaturated (non-aromatic) carbocyclic rings containing 3-12 members, either monocyclic or polycyclic, including spiro (sharing atoms) or fused (sharing at least one bond) carbocyclic rings, which may be optionally substituted. Examples of cycloalkyl groups include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclopenten-1-yl, cyclopenten-2-yl, cyclopenten-3-yl, cyclohexyl, cyclohexen-1-yl, cyclohexen-2-yl, cyclohexen-3-yl, cycloheptyl, and the like. When a cycloalkyl group is located between two functional groups, the term cycloalkylene may also be used. "C m ~C n Cycloalkyl" and "C m ~C n The term "cycloalkylene" refers to a cycloalkyl or cycloalkylene group having from the indicated number "m" to the indicated number "n" carbon atoms in the ring structure, respectively.

[0159] As used herein, the term "heterocycloalkyl" or "heterocycloalkylene" refers to a group containing a saturated or partially unsaturated (non-aromatic) carbocyclic ring containing 3 to 12 members, either monocyclic or polycyclic, including spiro (sharing one atom) or fused (sharing at least one bond) carbocyclic rings, which may be optionally substituted, and in which one or more atoms in the ring structure are substituted or unsubstituted heteroatoms (e.g., N, O, S, or P) or groups containing such heteroatoms (e.g., NH, NR x (R x is an alkyl, acyl, aryl, heteroaryl or cycloalkyl group), PO2, SO, SO2, and other similar groups. The heterocycloalkyl group may be linked to a carbon atom or, if possible, a heteroatom (e.g., via a nitrogen atom). The term heterocycloalkyl includes both unsubstituted and substituted heterocycloalkyl groups. When a heterocycloalkyl group is located between two functional groups, the term heterocycloalkylene may also be used. "C m ~C n Heterocycloalkyl" and "C m ~C n The term "heterocycloalkylene" refers to a heterocycloalkyl or heterocycloalkylene group having from the indicated number "m" to the indicated number "n" carbon atoms and heteroatoms, respectively, in the ring structure.

[0160] As used herein, the term "aryl" or "aromatic" refers to an aromatic group having 4n+2 π (pi) electrons (n ​​is an integer from 1 to 3) of a monocyclic or conjugated polycyclic ring system (fused or non-fused) with a total of 6 to 12 ring members. Polycyclic systems contain at least one aromatic ring. The group may be directly linked or bonded through a C1-C3 alkyl group. The term "aryl" or "aromatic" also includes substituted and unsubstituted groups. Examples of aryl groups include, but are not limited to, phenyl, benzyl, phenethyl, 1-phenylethyl, tolyl, naphthyl, biphenyl, terphenyl, indenyl, benzocyclooctenyl, benzocycloheptenyl, azulenyl, acenaphthylenyl, fluorenyl, phenanthrenyl, anthracenyl, perylenyl, and the like. When an aryl group is located between two functional groups, the term arylene may also be used. "C m ~C n aryl" or "C m ~C n Aromatic" and "C m ~C n The term "arylene" refers to aryl or aromatic and arylene groups having from the indicated number "m" to the indicated number "n" carbon atoms in the ring structure, respectively.

[0161] The terms "heteroaryl," "heteroarylene," or "heteroaromatic" refer to a monocyclic or conjugated polycyclic ring system (fused or non-fused), having 4n+2 π (pi) electrons, where n is an integer from 1 to 3, and containing 1 to 6 substituted or unsubstituted heteroatoms (e.g., N, O, or S) or groups containing such heteroatoms (e.g., NH, NR x (R xrefers to aromatic groups having 5 to 12 ring members, including alkyl, acyl, aryl, heteroaryl or cycloalkyl groups, SO, and other similar groups. Polycyclic systems contain at least one heteroaromatic ring. Heteroaryls may be directly linked or bonded via a C1-C3 alkyl group (also called heteroarylalkyl or heteroaralkyl). Heteroaryl groups may be linked to a carbon atom or, if possible, a heteroatom (e.g., via a nitrogen atom). "C m ~C n The term "heteroaryl" refers to a heteroaryl group having from the indicated number "m" to the indicated number "n" carbon atoms and heteroatoms in the ring structure.

[0162] As used herein, the term "substituted" means that one or more hydrogen atoms on the specified group are replaced by suitable substituents. Examples of substituents include halogen atoms (i.e., F, Cl, Br or I) and cyano, amido, nitro, trifluoromethyl, lower alkyl, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, lower alkoxy, aryloxy, benzyloxy, benzyl, alkoxycarbonyl, sulfonyl, sulfonate, silane, siloxane, phosphonato, phosphinato and other similar groups. These substituents may also be substituted where possible, for example, when the group contains an alkyl group, an alkoxy group, an aryl group, etc.

[0163] The present technology relates to plastic ionic crystals that include at least one delocalized anion paired with at least one guanidine, amidine, or phosphazene organic superbase derived cation. For example, the plastic ionic crystals can be monocationic or multicationic.

[0164] According to a variant of interest, the plastic ionic crystal may be a monocationic plastic ionic crystal comprising a delocalized anion paired with a cation derived from a guanidine, amidine or phosphazene organic superbase, the cation may be a protic cation derived from a guanidine, amidine or phosphazene organic superbase, and the plastic ionic crystal may be a protic monocationic plastic ionic crystal.

[0165] According to another variant of the object, the plastic ionic crystal can be a multicationic plastic ionic crystal, comprising at least two delocalized anions, each paired with a cationic moiety of a guanidine, amidine or phosphazene organic superbase-derived cation.For example, the multicationic plastic ionic crystal can be a dicationic, tricationic, tetracationic, pentacationic or hexacationic plastic ionic crystal.It should be understood that the cationic moieties are linked together by an organic bridging group that separates said cationic moieties.

[0166] In one example, the delocalized anion is trifluoromethanesulfonate (or triflate) [TfO]. - , Bis(trifluoromethanesulfonyl)imide [TFSI] - , bis(fluorosulfonyl)imide [FSI] - , 2-trifluoromethyl-4,5-dicyanoimidazolate [TDI] - , hexafluorophosphate [PF6] - and tetrafluoroborate [BF4] - According to one example, the delocalized anion may be selected from the group consisting of [TFSI] - and [FSI] - According to a variant of interest, the delocalized anion may be selected from the group consisting of [FSI] - It is.

[0167] By way of another example, a guanidine, amidine or phosphazene organic superbase may be selected for its affinity for hydrogen ions in organic solvents and its ability to delocalize the charge of the protonated cation form. For example, the guanidine, amidine or phosphazene organic superbase may bond a hydrogen cation to the nitrogen lone pair.

[0168] By way of another example, the guanidine, amidine or phosphazene organic superbase may have an acyclic, monocyclic, or polycyclic structure.

[0169] According to another example, the guanidine, amidine or phosphazene organic superbase can be selected from the group consisting of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), 2-tert-butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-diazaphosphorine (BEMP), tert-butylimino-tri(pyrrolidino)phosphorane (BTPP), and tert-butylimino-tris(dimethylamino)phosphorane (P1-t-Bu). According to the variant of interest, the organic superbase can be DBU or BEMP.

[0170] By way of another example, a cation derived from a guanidine, amidine, or phosphazene organic superbase can be the protic cation.

[0171] According to another example, the guanidine, amidine or phosphazene organic superbase cation may include at least one crosslinkable functional group. For example, the crosslinkable functional group may be selected from the group consisting of cyanate groups, acrylate groups, and methacrylate groups. According to a variant of interest, the crosslinkable functional group may be selected from the group consisting of C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate, carbonyloxy-C1~C 10Alkyl-acrylate, carbonylamino-C1~C 10 Alkyl-methacrylate, and carbonylamino-C1-C 10 Of course, at least partially crosslinked versions of these crosslinkable groups are also intended to be included in this definition.

[0172] According to another example, the guanidine, amidine or phosphazene organic superbase derived cation is an amidine organic superbase derived cation of formula 1: [ka] (In the formula, A together with the attached CN group forms an optionally substituted saturated, unsaturated or aromatic ring containing 4 to 8 members; B, together with the attached amidino group, forms an optionally substituted unsaturated non-aromatic ring containing 4 to 8 atoms. (In the formula, Plastic ion crystals are monocationic plastic ion crystals, R 1 is a hydrogen atom or C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-acrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate, and carbonyloxy-C1-C 10 or a linear or branched substituent selected from alkyl-acrylate; Plastic ion crystals are multicationic plastic ion crystals, R 1 is an optionally substituted organic bridging group separating two or more cations, and may be a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10Alkyleneoxy)C1~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene, and C3-C 12 heterocycloalkylene) It could be.

[0173] By way of another example, A may contain a heteroatom or a heteroatom-containing group. A may be any of C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene, or C3-C 12 It may be further fused to a heterocycloalkylene.

[0174] In another example, B may be monounsaturated or polyunsaturated and may be C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene, or C3-C 12 It may be further fused to a heterocycloalkylene.

[0175] According to another example, the cation derived from a guanidine, amidine or phosphazene organic superbase is a cation of formula 2-8: [ka] [ka] (In the formula, Plastic ion crystals are monocationic plastic ion crystals, R 1 is a hydrogen atom or C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonylamino-C1~C 10 Alkyl-methacrylate, carbonylamino-C1~C 10Alkyl-acrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate, and carbonyloxy-C1-C 10 or a linear or branched substituent selected from alkyl-acrylate; Plastic ion crystals are multicationic plastic ion crystals, R 1 is an optionally substituted organic bridging group separating at least two of the cations, and is a linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene, and C3-C 12 heterocycloalkylene) It could be one of the following.

[0176] In another example, a cation derived from a guanidine, amidine or phosphazene organic superbase is represented by the formula [R 1 -DBU] + , [R 1 -DBN] + , [R 1 -MTBD] + , [R 1 -BEMP] + , [R 1 -BTPP] + and [R 1 -P1-t-Bu] + According to a variant of interest, the cation derived from a guanidine, amidine or phosphazene organic superbase may be selected from the group consisting of [R 1 -DBU] + or [R 1 -BEMP] + It is.

[0177] In another example, a cation derived from a guanidine, amidine or phosphazene organic superbase is reacted with [H-DBU] + , [H-DBN] + , [H-MTBD] + , [H-BEMP] + , [H-BTPP] + and [H-P1-t-Bu] + According to a variant of interest, the cation derived from a guanidine, amidine or phosphazene organic superbase may be selected from the group consisting of [H-DBU] + or [H-BEMP] + It is.

[0178] According to another example, a plastic ionic crystal may be formed according to formula 9: [ka] (In the formula, A, B and R 1 is as defined herein; X - is a delocalized anion as defined herein. It may be of the following type.

[0179] According to another example, the plastic ionic crystal is a plastic ionic crystal of formula 10-16: [ka] [ka] (In the formula, R 1 is as defined herein; X - is a delocalized anion as defined herein. It could be one of the following.

[0180] In another example, a plastic ionic crystal is formed by 1 -DBU][OTf], [R 1 -DBU][TFSI],[R 1 -DBU][FSI], [R 1-DBU][TDI],[R 1 -DBU][PF6], [R 1 -DBU][BF4], [R 1 -DBN][OTf], [R 1 -DBN][TFSI], [R 1 -DBN][FSI], [R 1 -DBN][TDI], [R 1 -DBN][PF6], [R 1 -DBN][BF4], [R 1 -MTBD][OTf], [R 1 -MTBD][TFSI],[R 1 -MTBD][FSI],[R 1 -MTBD][TDI],[R 1 -MTBD][PF6], [R 1 -MTBD][BF4], [R 1 -BEMP][OTf], [R 1 -BEMP][TFSI], [R 1 -BEMP][FSI], [R 1 -BEMP][TDI], [R 1 -BEMP][PF6], [R 1 -BEMP][BF4], [R 1 -P1-t-Bu][OTf], [R 1 -P1-t-Bu][TFSI], [R 1 -P1-t-Bu][FSI], [R 1 -P1-t-Bu][TDI], [R 1 -P1-t-Bu][PF6], [R 1 -P1-t-Bu][BF4], [R 1 -BTPP][OTf], [R 1 -BTPP][TFSI], [R 1 -BTPP][FSI], [R 1 -BTPP][TDI], [R 1 -BTPP][PF6], and [R 1 According to a variant of the subject matter, the plastic ionic crystal may be selected from the group consisting of [R 1 -DBU][FSI] or [R 1 -BEMP][FSI].

[0181] According to another example, plastic ionic crystals are [H-DBU][OTf], [H-DBU][TFSI], [H-DBU][FSI], [H-DBU][TDI], [H-DBU][PF6], [H-DBU][BF4], [H-DBN][OTf], [H-DBN][TFSI], [H-DBN][FSI], [H-DBN][TDI], [H-DBN][PF6], [H-DBN][BF4], [H-MTBD][OTf], [H-MTBD][TFSI], [H-MTBD][FSI], [H-MTBD][TDI], [H-MTBD][PF6], [H-MTBD][BF4], [H-BEMP][OTf], [H-BEMP][TFSI], [H-BEMP][FSI], [H-BEMP][TDI], [H-BEMP][PF6], [H-BEMP][BF4], [H-P1-t-Bu][OTf], [H-P1-t-Bu][TFSI], [H-P1-t-Bu][FSI], [H-P1-t-Bu][TDI], [H-P1-t-Bu][PF6], [H-P1-t-Bu][BF4], [H-BTPP][OTf], [H-BTPP][TFSI], [H-BTPP][FSI], [H-BTPP][TDI], [H-BTPP][PF6], and [H-BTPP][BF4]. According to a variant of interest, the plastic ionic crystal is [H-DBU][FSI] or [H-BEMP][FSI].

[0182] The present technology also provides a bis-silylated compound of formula 17: [ka] (In the formula, Z is a straight or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10a substituted or unsubstituted organic group selected from alkylene, linear or branched polyethers, linear or branched polycarbonates, linear or branched polythiocarbonates, linear or branched polyamides, linear or branched polyimides, linear or branched polyurethanes, linear or branched polysiloxanes, linear or branched thioethers, linear or branched polyphosphazenes, linear or branched polyesters, and linear or branched polythioesters; R 2 is independently, at each occurrence, selected from the group consisting of alkyl groups, aryl groups, and arylalkyl groups. The present invention relates to a stabilized intermediate ion-neutral complex obtained by the reaction of a cation derived from a guanidine, amidine or phosphazene organic superbase as described herein, a proton source and a delocalized anion as described herein in the presence of

[0183] According to one example, the bis-silylated compound of formula 17 can be selected from the group consisting of glycerol (glycerin), 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,2-propanediol (or propylene glycol (PG)), 1,2-butanediol, 2,3-butanediol (or dimethylene glycol), 1,3-butanediol (or butylene glycol), 1,2-pentanediol, ethoxyhexadiol, p-menthane-3,8-diol, 2-methyl-2,4-pentane ... The bis-silylated derivatives of a compound containing at least two hydroxyl groups are selected from the group consisting of ethanediol, polycaprolactone diol, ethylene glycol (1,2-ethanediol), diethylene glycol (or ethylene diglycol), triethylene glycol, tetraethylene glycol, pentaethylene glycol, polyethylene glycol, 2,2,3,3,4,4,5,5-octafluorohexane-1,6-diol, and other similar glycols and diols, or a combination of at least two of these. According to a variant of interest, the compound containing at least two hydroxyl groups is diethylene glycol or glycerol.

[0184] According to another example, the stabilized intermediate ion-neutral complex is a complex of formula 18-24: [ka] (In the formula, Z, X - and R 2 is as defined herein) It could be one of the following.

[0185] According to one example, the silane group of the bis-silylated compound of formula 17 can be cleaved, and the NH proton of the cation from the guanidine, amidine, or phosphazene organic superbase can participate in hydrogen bonding to form an NHO-stabilized intermediate ion-neutral complex. For example, only about 1% of the bis-silylated compounds of formula 17 end up with a cleaved silane group. For example, the NHO-stabilized intermediate ion-neutral complex is a by-product of the reaction.

[0186] According to another example, NHO-stabilized intermediate ion-neutral complexes are complexes of formulas 25-31: [ka] [ka] (In the formula, Z and R 2 is as defined herein) It could be one of the following.

[0187] The present technology also relates to a plastic ionic crystal composition comprising at least one plastic ionic crystal as defined herein and at least one additional component and / or at least one polymer.

[0188] According to one example, the additional component may be selected from the group consisting of a solvent, an ion conductor, an inorganic particle, a glass particle, a ceramic particle (e.g., nanoceramic), a plasticizer, and other similar components, or a combination of at least two of these. For example, the additional component may be a filler additive and may include metal oxide particles or nanoparticles. For example, the filler additive may include titanium dioxide (TiO2), alumina (Al2O3), and / or silicon dioxide (SiO2) particles or nanoparticles.

[0189] According to another example, the polymer may be a polymer, such as a polymer commonly used in solid polymer electrolytes (SPEs). A solid polymer electrolyte may generally include one or more optionally crosslinked solid polar polymers, and a salt (e.g., as defined above). A polyether-type polymer, such as a polymer based on poly(ethylene oxide) (PEO), may be used, although several other compatible polymers are known for the preparation of solid polymer electrolytes and are also contemplated. The polymer may be crosslinked. Examples of such polymers include branched polymers, such as star polymers or comb polymers, such as those described in U.S. Pat. No. 7,897,674 B2 (Zaghib et al.) (US'674).

[0190] According to some examples, the polymer can be a block copolymer composed of at least one lithium ion solvating segment and, optionally, at least one crosslinkable segment. For example, the lithium ion solvating segment can be a repeating unit of formula 32: [ka] (In the formula, R 3 is a hydrogen atom, C1-C 10 Alkyl group or -(CH2-OR 4 R 5 ) group; R 4 is (CH2-CH2-O) m and; R 5is a hydrogen atom and C1-C 10 alkyl groups; y is an integer selected from the range of 10 to 200,000; m is an integer selected from the range of 0 to 10. The copolymer is selected from homopolymers or copolymers having the formula:

[0191] According to another example, the crosslinkable segment of the copolymer is a polymer segment that includes at least one functional group that is multi-dimensionally crosslinkable by irradiation or heat treatment.

[0192] According to another example, the concentration of the polymer in the plastic ionic crystal composition may be at least 10% by weight. For example, the concentration of the polymer in the plastic ionic crystal composition may be in the range of about 5% to about 45% by weight, or about 10% to about 45% by weight, or about 15% to about 45% by weight, or about 20% to about 45% by weight, or about 25% to about 45% by weight, or about 30% to about 45% by weight, or about 35% to about 45% by weight, or about 40% to about 45% by weight, including the upper and lower limits. According to a variant of interest, the plastic ionic crystal composition comprises about 40% by weight of the polymer and 60% by weight of the plastic ionic crystal described herein. It should be understood that the optimal concentration of the polymer in the plastic ionic crystal composition depends on the polymer used.

[0193] According to another example, the additional component may be an inorganic particle comprising a compound having a garnet, NASICON-type, LISICON-type, thio-LISICON-type, LIPON-type, perovskite-type, antiperovskite-type, or argyrodite-type structure, or a compound of MPS-type, MPSO-type, MPSX-type, MPSOX-type (wherein M is an alkali metal or alkaline earth metal and X is F, Cl, Br, I, or a combination of at least two of these) in a crystalline, amorphous, and / or glass-ceramic phase, or a mixture of at least two of these.

[0194] According to another example, the additional component is a compound having the formula MLZO (e.g., M7La3Zr2O 12 , M (7-a) La3Zr2Al b O 12 , M (7-a) La3Zr2Ga b O 12 , M (7-a) La3Zr (2-b) Ta b O 12 and M. (7-a) La3Zr (2-b) Nb b O 12 );MLTaO (e.g., M7La3Ta2O 12 , M5La3Ta2O 12 and M6La3Ta 1.5 Y 0.5 O 12 );MLSnO (e.g., M7La3Sn2O 12 );MAGP(e.g., M 1+a Al a Ge 2-a (PO4)3); MATP (e.g., M 1+a Al a Ti 2-a (PO4)3);MLTiO (e.g., M 3a La (2 / 3-a) TiO3);MZP (e.g., M a Zr b (PO4) c );MCZP (e.g., M a Ca b Zr c (PO4) d );MGPS(e.g., M 10 GeP2S 12 M a Ge b P c S d );MGPSO(e.g., M a Ge b P c S d O e ); MSiPS (e.g., M 10 SiP2S 12 M a S b P c S d);MSiPSO (e.g., M a S b P c S d O e ); MSnPS (e.g., M 10 SnP2S 12 M a Sn b P c S d );MSnPSO (e.g., M a Sn b P c S d O e );MPS(e.g., M7P3S 11 M a P b S c );MPSO (e.g., M a P b S c O d );MZPS(e.g., M a Zinc b P c S d );MZPSO(e.g., M a Zinc b P c S d O e );xM2S-yP2S5;xM2S-yP2S5-zMX;xM2S-yP2S5-zP2O5;xM2S-yP2S5-zP2O5-wMX;xM2S-yM2O-zP2S5;xM2S- yM2O-zP2S5-wMX;xM2S-yM2O-zP2S5-wP2O5;xM2S-yM2O-zP2S5-wP2O5-vMX;xM2S-ySiS2;MPSX (for example, M7P3S 11 X, M7P2S8X and M6PS5X a P b S c X d );MPSOX(For example, M a P b S c O d X e );MGPSX(For example, M a Ge b P c S d X e);MGPSOX(For example, M a Ge b P c S d O e X f );MSiPSX(e.g., M a S b P c S d X e );MSiPSOX(e.g., M a S b P c S d O e X f );MSnPSX (e.g., M a Sn b P c S d X e );MSnPSOX (e.g., M a Sn b P c S d O e X f );MZPSX(For example, M a Zinc b P c S d X e );MZPSOX(For example, M a Zinc b P c S d O e X f );M3OX;M2HOX;M3PO4;M3PS4;and M a PO b N c (a=2b+3c-5) (In the formula, M is an alkali metal ion, an alkaline earth metal ion, or a combination thereof, and when M comprises an alkaline earth metal ion, the number of M's is adjusted to achieve electroneutrality; X is selected from F, Cl, Br, I, or combinations thereof; a, b, c, d, e, and f are numbers other than 0 and are independently selected in each formula to achieve electroneutrality; v, w, x, y, and z are numbers other than 0 and are independently selected in each formula to provide a stable compound. The inorganic particles may be of a crystalline phase, an amorphous phase, and / or a glass-ceramic phase, or a mixture of at least two of these, comprising at least one of the inorganic compounds of formula (I).

[0195] According to another example, the additional component can be a ceramic or a glass ceramic. For example, the additional component can be Li 10 GeP2S 12 , Li6PS5Cl, Li2S-P2S5, Li7P3S 11 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li 9.6 P3S 12 , Li 3.25 P 0.95 The ceramic or glass-ceramic may be a sulfide-based ceramic or glass-ceramic, such as Li6PS5Cl, S4, and other similar ceramics and glass-ceramics. According to a variant of interest, the sulfide-based ceramic or glass-ceramic is Li6PS5Cl. The concentration of the ceramic or glass-ceramic in the plastic ionic crystal composition may be at least 50% by weight. For example, the concentration of the ceramic or glass-ceramic in the plastic ionic crystal composition may be in the range of about 50% to about 95% by weight, or about 55% to about 95% by weight, or about 60% to about 95% by weight, or about 65% to about 95% by weight, or about 70% to about 95% by weight, or about 75% to about 95% by weight, or about 80% to about 95% by weight, or about 85% to about 95% by weight, or about 90% to about 95% by weight, including the upper and lower limits. According to a variant of the object, the plastic ionic crystal composition comprises about 90% by weight of Li6PS5Cl and 10% by weight of the plastic ionic crystal described herein. It should be understood that the optimal concentration of the additional components in the plastic ionic crystal composition depends on the additional components used (e.g., on their particle size, their specific surface area, etc.).

[0196] According to one example, plastic ionic crystals can be prepared by any suitable synthesis method. For example, synthesis of plastic ionic crystals can include at least one of a proton exchange reaction, a counterion exchange reaction, and any other suitable reaction.

[0197] According to another example, a method for synthesizing a protonically plastic ionic crystal may include at least two synthesis steps. The first step may involve reacting a neutral organic superbase of the amidine, guanidine or phosphazene type with at least one proton source to form a complex, adduct or ion pair containing a protonated cation. For example, the organic superbase may be selected for its ability to remove protons (or affinity for protons). For example, the organic superbase may be a non-nucleophilic organic superbase or a weakly nucleophilic organic superbase. According to a variant of interest, the organic superbase may be selected from the group consisting of DBU, DBN, MTBD, BEMP, BTPP, and P1-t-Bu or a derivative thereof. For example, the organic superbase may be DBU or BEMP. For example, the second step may involve a counterion exchange reaction between the complex, adduct or ion pair containing a protonated cation formed in the first step and an ionic salt based on the above-mentioned delocalized anion. For example, the ionic salt may be an alkali or alkaline earth metal salt, such as lithium, sodium, potassium, calcium, or magnesium salt. For example, the ionic salt may be a lithium salt selected from the group consisting of lithium trifluoromethanesulfonate (LiSO3CF3) (LiOTf), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4). According to a variant of interest, the lithium salt is LiFSI.

[0198] According to another example, the plastic ionic crystal can be a proton plastic ionic crystal formed by proton transfer from a Bronsted acid to a Bronsted base. For example, the Bronsted base can be a neutral organic superbase of the amidine, guanidine or phosphazene type, and can be selected for its ability to remove protons (or affinity for protons). According to a variant of interest, the organic superbase can be selected from the group consisting of DBU, DBN, MTBD, BEMP, BTPP, and P1-t-Bu, or derivatives thereof. For example, the organic superbase can be DBN or BEMP. According to another variant of the object, the Bronsted acid may be selected from the group consisting of trifluoromethanesulfonic acid (TfOH), bis(trifluoromethanesulfonyl)imidic acid (HTFSI), bis(fluorosulfonyl)imidic acid (HFSI), 2-(trifluoromethyl)-1H-imidazole-4,5-dicarbonitrile (HTDI), hexafluorophosphoric acid (HPF6), and tetrafluoroboric acid (HBF4). According to a variant of the object, the Bronsted acid is HFSI.

[0199] Thus, the present technology also provides a method for preparing a plastic ionic crystal or a plastic ionic crystal composition as defined herein, comprising the steps of: (i) reacting at least one of the organic superbases described above with a Bronsted acid based on a delocalized anion as defined herein to form plastic ionic crystals; The present invention relates to a method comprising the steps of:

[0200] The present technology therefore also provides a method for preparing a plastic ionic crystal or a plastic ionic crystal composition as defined herein, comprising the steps of: (i) reacting at least one of the organic superbases described above with a proton source to form at least one complex comprising a protonated cation and a counterion; and (ii) reacting the complex comprising the protonated cation and the counterion with at least one ionic salt based on the delocalized anion described above. The present invention relates to a method comprising the steps of:

[0201] According to one example, the organic superbase is a neutral organic superbase of the amidine, guanidine or phosphazene type. According to a variant of interest, the organic superbase is selected from the group consisting of DBU, DBN, MTBD, BEMP, BTPP, and P1-t-Bu, or derivatives thereof. For example, the organic superbase can be DBU or BEMP.

[0202] According to another example, the method further comprises a step of preparing an organic superbase, which is carried out before step (i). In some examples, the organic superbase can be a neutral polycyclic amidine organic superbase prepared by condensation of an aromatic dialdehyde with a 1,2-diamine. For example, the neutral polycyclic amidine organic superbase can be prepared by the method described by Braddock et al. (Braddock, DC et al. "The reaction of aromatic dialdehydes with enantiopure 1,2-diamines: an expeditious route to enantiopure tricyclic amidines." Tetrahedron: Asymmetry 21.24 (2010): 2911-2919).

[0203] By way of another example, an ionic salt based on a delocalized anion as defined herein can be an alkali or alkaline earth metal salt, such as a lithium, sodium, potassium, calcium, or magnesium salt, based on a delocalized anion as defined herein. For example, the ionic salt can be of the formula M n+ [(FSI) n ] n- (In the formula, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ According to a variant of the invention, the cations may be selected from the group consisting of alkali or alkaline earth metal ions. n+ Li + It is.

[0204] According to another example, the two reaction steps may be carried out sequentially in time with each other, simultaneously or partially overlapping. According to a variant of the object, the two reaction steps are carried out sequentially, with the step of reacting at least one organic superbase with a proton source being carried out before the step of reacting the complex comprising the protonated cation and the counterion with the ionic salt based on the delocalized anion. According to another variant of the object, all reactants may be mixed together and left to react under suitable reaction conditions.

[0205] According to another example, the synthesis may be carried out in the presence of a solvent. For example, the solvent may act as a source of protons and may be selected for its ability to readily donate protons or to stabilize the base and / or the solvent-conjugated acid cation. For example, the stabilization of the base and / or the solvent-conjugated acid cation may be achieved through solvation, non-covalent interactions (e.g., hydrogen bonds and dipole-dipole interactions), or van der Waals interactions. Without wishing to be bound by theory, the ability to efficiently solubilize, and thus improve the solvation stability of the protonated form of the organic superbase, may significantly improve the reaction yield. For example, the solvent may be a polar solvent selected from the group consisting of dichloromethane (DCM), dimethyl carbonate (DMC), acetonitrile (ACN), ethanol (EtOH), and miscible combinations of at least two of these. According to a variant of interest, the solvent may be ACN.

[0206] According to one example of interest, the synthesis of plastic ionic crystals can be carried out by the method shown in Scheme 1 (reaction by-products not shown): [ka] Scheme 1 (In the formula, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ions).

[0207] According to the purpose variant, M n+ Li + It is.

[0208] According to another example, the synthesis can be carried out in the presence of a second proton source, such as a suitable acid. The second proton source can be selected, for example, for its ability to readily donate a proton or to stabilize the base and / or solvent conjugate acid cation. For example, the second proton source can also act as an activator and / or catalyst to obtain plastic ionic crystals, which can substantially improve the reaction yield. Examples of second proton sources include, but are not limited to, carboxylic acids (e.g., formic acid, acetic acid, propionic acid, lactic acid and trifluoroacetic acid), p-toluenesulfonic acid (or tosylic acid), sulfuric acid, hydroiodic acid, hydrobromic acid, hydrochloric acid, nitric acid, hydrofluoric acid, and other similar acids. According to a variant of interest, the acid is formic acid.

[0209] According to one example of interest, the synthesis of plastic ionic crystals can be carried out by the method shown in Scheme 2 (reaction by-products not shown): [ka] Scheme 2 (In the formula, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ ions).

[0210] According to another example, synthesis can be carried out in the presence of an activator that can also act as a stabilizer and / or proton source. The activator can react with an organic superbase to form a stable intermediate non-covalent complex. For example, the activator can substantially promote the formation of plastic ionic crystals through the formation of said stable intermediate non-covalent complex by electrophilic nucleophilic activation. For example, the stable intermediate non-covalent complex can be an NHO stabilized intermediate ion-neutral complex. For example, the activator can be the above-mentioned bis-silylated compound.

[0211] According to one example of interest, the synthesis of plastic ionic crystals can be carried out by the method shown in Scheme 3 (reaction by-products not shown): [ka] Scheme 3 (In the formula, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ ions; R 2 is as defined herein).

[0212] According to another example, the method further comprises a step of preparing a bis-silylated compound. The preparation of the bis-silylated compound can be carried out by silylation of a compound comprising at least two hydroxyl groups that can be derivatized by a silylation reagent, for example, the compound comprising at least two hydroxyl groups can be as described above. For example, the silylation reaction can be carried out by a base-catalyzed silylation reaction, which can involve the replacement of an acidic hydrogen (or active hydrogen) with a silyl group (e.g., an alkylsilyl group), for example, a trialkylsilyl group. For example, a compound comprising at least two hydroxyl groups can be deprotonated with a base and then treated with at least one silylation reagent. The base-catalyzed silylation reaction can be carried out in the presence of any known compatible base. For example, the base can be a nucleophilic Lewis base, such as imidazole, 4-dimethylaminopyridine (DMAP), other similar nucleophilic Lewis bases, and combinations thereof. According to a variant of interest, the base is imidazole. For example, the silylation reaction can be carried out in a polar aprotic solvent such as tetrahydrofuran (THF), N,N-dimethylformamide (DMF), dichloromethane (DCM), dimethylsulfoxide (DMSO) or a miscible combination of at least two of these. According to the variant of interest, the aprotic solvent is THF, DCM or a combination of DCM and DMF with a significant predominance of DCM.

[0213] For example, a silylation reagent may be selected for its reactivity and selectivity towards compounds containing at least two hydroxyl groups, the stability of the silylated derivative and the reaction by-products. For example, a universal silylation reagent may be used to derivatize the hydroxyl groups of a compound containing at least two hydroxyl groups. Non-limiting examples of silylation reagents include trialkylsilyl chloride, trimethylsilyl chloride (TMS-Cl), triethylsilyl chloride (TES-Cl), isopropyldimethylsilyl chloride (IPDMS-Cl), diethylisopropylsilyl chloride (DEIPS-Cl), tert-butyldimethylsilyl chloride (TBDMS-Cl or TBS-Cl), tert-butyldiphenylsilyl chloride (TBDPS-Cl or TPS-Cl), triisopropylsilyl chloride (T ... Examples of suitable silyl ethers include N,O-bis(tert-butyldimethylsilyl)acetamide (BSA), N-methyl-N-(trimethylsilyl)trifluoroacetamide (MSTFA), N-(trimethylsilyl)dimethylamine (TMSDEA), N-(trimethylsilyl)imidazole (TMSI or TSIM), N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) and N-methyl-N-(trimethylsilyl)acetamide (MSA). According to the variant of interest, the silylation reagent comprises a trialkylsilyl chloride, such as TMS-Cl or TBDMS-Cl.

[0214] For example, TBDMS-Cl can be used to replace the active hydrogen on the hydroxyl group, and the synthesis of the bis-silylated compound can be carried out by the silylation reaction shown in Scheme 4(a) or 4(b): [ka] Scheme 4(a) [ka] Scheme 4(b) (In the formula, Z is a straight or branched C1-C 10Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 is a substituted or unsubstituted organic group selected from alkylene, linear or branched polyethers, linear or branched polycarbonates, linear or branched polythiocarbonates, linear or branched polyamides, linear or branched polyimides, linear or branched polyurethanes, linear or branched polysiloxanes, linear or branched thioethers, linear or branched polyphosphazenes, linear or branched polyesters, and linear or branched polythioesters.

[0215] A typical example of a silylation reaction using TBDMS-Cl as the silylation reagent and involving nucleophilic attack on silicon is shown in Scheme 4(a). For example, one equivalent of a compound containing at least two hydroxyl groups can react with two equivalents of TBDMS-Cl to form a bis-silylated compound and hydrochloric acid (HCl) as a reaction by-product. It should be understood that the reaction involves one silyl group per hydroxyl group that is derivatized.

[0216] Another example of a silylation reaction is described by Sharpless et al. (Sharpless, KB et al. "SuFEx-Based Synthesis of Polysulfates" Angewandte Chemie International Edition 53.36 (2014): 9466-9470 (supplementary material)). An example of this silylation reaction is shown in Scheme 4(b). For example, the silylation reagent can be added in a molar ratio of about 1:1 or about 1:0.9 (-OH group to be derivatized): (silyl group). Alternatively, the silylation reagent can be added in excess. For example, the amount of silylation reagent can range from about 2 equivalents to about 5 equivalents (including upper and lower limits) per equivalent of a compound containing at least two hydroxyl groups. For example, the amount of silylation reagent can range from about 2 equivalents to about 4.5 equivalents, or from about 2 equivalents to about 4 equivalents, or from about 2 equivalents to about 3.75 equivalents, or from about 2 equivalents to about 3.5 equivalents (including upper and lower limits) per equivalent of a compound containing at least two hydroxyl groups. According to the intended variation, the amount of silylation reagent can range from about 2.2 equivalents to about 3.3 equivalents per equivalent of a compound containing at least two hydroxyl groups when the compound contains two and three hydroxyl groups, respectively.

[0217] According to another example, the silylation reaction can be carried out at room temperature for a period of time sufficient to allow for substantially complete reaction. For example, the silylation reaction can be carried out for at least 15 hours when carried out according to the reaction shown in Scheme 4(a). For example, the silylation reaction can be carried out for a period of time ranging from about 15 hours to about 24 hours, inclusive. Alternatively, the silylation reaction can be carried out for about 3 hours when carried out according to the reaction shown in Scheme 4(b).

[0218] It should be understood that the use of DCM as a solvent has a significant effect on the reaction rate, and thus DCM may be used for larger scale synthesis of bis-silylated compounds compared to other solvents such as THF or DMF.

[0219] Thus, by way of another example, the preparation of plastic ionic crystals or plastic ionic crystal compositions as defined herein may involve protonation and anion exchange reactions.

[0220] A general example of this mechanism is shown in Scheme 3 and involves reacting DBU with a metal bis(fluorosulfonyl)imide in the presence of the bis-silylated compound from Scheme 4(a) or 4(b) to give plastic ionic crystals and by-products (not shown in Scheme 3).

[0221] According to another example, the activator (i.e., the bis-silylated compound) can be reacted with an approximately equimolar amount of the organic superbase. Alternatively, the organic superbase can be added in excess, for example, the excess can range from about 0.01 mol% to about 10 mol%, inclusive. According to a variation of interest, the activator can be reacted with an approximately equimolar amount of the organic superbase.

[0222] According to another example, both reaction steps can be carried out at a temperature high enough to allow substantially complete reaction and for a sufficient period of time. For example, both reaction steps can be carried out at a temperature in the range of about 20°C to about 200°C, inclusive. For example, the two reaction steps can be carried out at a temperature in the range of about 40°C to about 80°C, or about 45°C to about 75°C, or about 50°C to about 70°C, or about 55°C to about 65°C, inclusive. For example, both reaction steps can be carried out for at least 4 days.

[0223] According to another example, the method further comprises a step for removing at least one by-product generated during any method step. For example, the removing step can be performed by distillation or evaporation. For example, the by-product can be removed at ambient atmospheric pressure or under vacuum, depending on the boiling point of the by-product to be removed. The by-product can be removed by washing with any suitable solvent that dissolves the by-product but does not dissolve the plastic ion crystals. For example, the by-product can also be removed by more than one method, if necessary. According to a variant of interest, the by-product can be removed by extraction, for example, by dissolving the by-product in DCM and extracting with water and brine.

[0224] According to another example, the method further comprises a functionalization step, for example the functionalization of the plastic ionic crystal, taking into account its crosslinking.For example, the functionalization of the plastic ionic crystal can be carried out as required, for example by introducing at least one functional group as defined above, for example a crosslinkable functional group, in order to functionalize the plastic ionic crystal.The crosslinkable functional group can be present on the cation of the plastic ionic crystal or on the side chain of the cation backbone.

[0225] According to another example, the reaction step and the functionalization step may be performed sequentially, simultaneously or partially overlapping with each other in time. According to a variant of the object, the reaction step and the functionalization step are performed sequentially, the reaction step being performed before the functionalization step. For example, the functionalization step is a post-functionalization step.

[0226] According to another example, the functionalization step can be carried out by a reaction between a protonated cation and at least one crosslinkable functional group. For example, the functionalization step can be carried out by a reaction between a protonated cation and a C1-C 10 Alkyl-acrylate, C1-C 10 Alkyl-methacrylate, carbonyloxy-C1~C 10 Alkyl-methacrylate, carbonyloxy-C1~C 10 Alkyl-acrylate, carbonylamino-C1~C 10 Alkyl-methacrylate, and carbonylamino-C1-C 10This can be carried out by reaction between at least one crosslinkable functional group selected from the group consisting of alkyl-acrylate groups.

[0227] According to another example, a post-functionalization step can be carried out according to the reaction shown in Scheme 5 (reaction by-products not shown): [ka] Scheme 5

[0228] According to another example, the method further comprises a step of coating the above-mentioned plastic ion crystal composition or suspension containing plastic ion crystals. For example, the coating step can be carried out by at least one of doctor blade coating method, comma coating method, reverse comma coating method, printing method such as gravure coating, or slot die coating method. According to a variant of the object, the coating step is carried out by doctor blade coating method or slot die coating method. According to one example, the plastic ion crystal composition or suspension containing plastic ion crystals can be coated on a substrate or support film (e.g., a substrate made of silicon, polypropylene or siliconized polypropylene). For example, the substrate or support film can be removed afterwards. According to another example, the plastic ion crystal composition or suspension containing plastic ion crystals can be directly coated on an electrode.

[0229] According to another example, the method further comprises drying the plastic ionic crystal composition or the plastic ionic crystal defined above. According to one example, the drying step can be carried out to remove residual solvent. According to another example, the drying step and the coating step can be carried out simultaneously and / or separately.

[0230] According to another example, the method further comprises a step of crosslinking the plastic ion crystal composition or the plastic ion crystal defined above. For example, the cation comprises at least one functional group that allows crosslinking of said plastic ion crystal. According to another example, the crosslinking step can be carried out by UV irradiation, by heat treatment, by microwave irradiation, under electron beam, by gamma radiation, or by X-ray irradiation. According to a variant of the object, the crosslinking step is carried out by UV irradiation. According to another variant of the object, the crosslinking step is carried out by heat treatment. According to another variant of the object, the crosslinking step is carried out under electron beam. According to another example, the crosslinking step can be carried out in the presence of a crosslinking agent, a thermal initiator, a photoinitiator, a catalyst, a plasticizer, or a combination of at least two of them. For example, the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone (Irgacure™ 651). For example, the plastic ion crystal composition or the plastic ion crystal can solidify after crosslinking.

[0231] The present technology also provides a method for preparing a multicationic plastic ion crystal or a multicationic plastic ion crystal composition as defined in the present application, comprising the steps of: (i) reacting the organic superbase with an organic bridging compound to form a multicationic complex comprising at least two organic superbase cationic moieties separated (or linked) by the organic bridging group and paired with a counterion; and (ii) reacting said multicationic complex with at least one ionic salt based on a delocalized anion as defined herein; The present invention relates to a method comprising the steps of:

[0232] According to one example, the organic superbase is a neutral amidine, guanidine or phosphazene type organic superbase. According to a variant of interest, the organic superbase is selected from the group consisting of DBU, DBN, MTBD, BEMP, BTPP and P1-t-Bu, or derivatives thereof. For example, the organic superbase can be DBU or BEMP.

[0233] According to another example, an organic bridging compound includes the organic bridging group described above and at least two anionic leaving groups. The anionic leaving groups of the organic bridging compound can be selected for their leaving group capabilities. Any compatible anionic leaving group is contemplated. Non-limiting examples of anionic leaving groups include F - , Cl - , Br - and I - According to the variant of interest, the anionic leaving group is Br - It is.

[0234] According to another embodiment, the organic bridging group is an optionally substituted organic bridging group, linear or branched C1-C 10 Alkylene, linear or branched C1-C 10 Alkyleneoxy C1~C 10 Alkylene, linear or branched poly(C1-C 10 Alkyleneoxy)C1~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C6-C 12 Arylene, C5~C 12 Heteroarylene, C3-C 12 Cycloalkylene, and C3-C 12 According to a variant of interest, the organic bridging group is selected from the group consisting of C6-C 12 In some examples, the organic bridging group is 1,2,4,5-tetrakis(bromomethyl)benzene.

[0235] According to another example, the two reaction steps may be carried out sequentially in time with each other, simultaneously or partially overlapping. According to a variant of the object, the two reaction steps are carried out sequentially, the step of reacting the organic superbase with the organic bridging compound being carried out before the step of reacting the multicationic complex with the ionic salt. According to another variant of the object, all reactants may be mixed together and left to react under suitable reaction conditions.

[0236] According to another example, the step of reacting the organic superbase with the organic crosslinking compound can be carried out in the presence of a solvent.For example, the solvent can be a polar solvent selected from the group consisting of DCM, DMC, ACN, EtOH, and miscible combinations of at least two of them.According to a variant of interest, the solvent can be DCM.

[0237] According to another example, the step of reacting the organic superbase with the organic bridging compound may be carried out in the presence of a base such as triethylamine (Et3N), N,N-diisopropylethylamine (iPr2NEt), pyridine, and pyridine derivatives. According to a variant of interest, the base is Et3N.

[0238] According to one example of interest, the synthesis of multicationic plastic ion crystals can be carried out by the method shown in Scheme 6 (reaction by-products not shown): [ka] Scheme 6 (In the formula, M n+ is Na + , K + , Li + , Ca 2+ and Mg 2+ ions).

[0239] According to another example, the step of reacting the organic superbase with the organic crosslinking compound can further include recovering the multicationic complex.For example, the step of recovering the multicationic complex can be performed by centrifugation.The centrifugation can be performed at a revolutions per minute and for a period of time sufficient to recover the multicationic complex.For example, the centrifugation can be performed at about 5000 rpm for about 10 minutes.

[0240] According to another example, the two reaction steps can be carried out at a temperature high enough and for a sufficient period of time to allow substantially complete reaction. For example, the step of reacting the organic superbase with the organic bridging compound can be carried out at room temperature for about 4 days. For example, the step of reacting the multicationic complex with the ionic salt can be carried out at room temperature for about 3 days.

[0241] According to another example, the method further comprises recovering the multicationic plastic ion crystals, for example by centrifugation. The centrifugation can be carried out at a revolutions per minute and for a period of time sufficient to recover the multicationic plastic ion crystals.

[0242] According to another example, the method further comprises drying the multicationic plastic ion crystals. The drying step can be carried out at a temperature high enough and for a period of time sufficient to substantially dry the multicationic plastic ion crystals. For example, the drying step can be carried out under vacuum at a temperature of about 45° C. for about 48 hours.

[0243] According to another example, the method further comprises removing at least one by-product generated during any method step. For example, the removing step can be carried out by distillation or evaporation. For example, the by-product can be removed at ambient atmospheric pressure or under vacuum, depending on the boiling point of the by-product to be removed. The by-product can be removed by washing with any suitable solvent that dissolves the by-product but does not dissolve the multicationic plastic ion crystals. For example, the by-product can also be removed by more than one method, if necessary. According to a variant of interest, the by-product can be removed by extraction, for example, by dissolving the product in DCM.

[0244] The present technology also relates to the use of a plastic ionic crystal composition or a plastic ionic crystal as defined above in electrochemical applications.

[0245] According to one example, the plastic ionic crystal composition or the plastic ionic crystal may be used in electrochemical cells, batteries, supercapacitors (e.g., carbon-carbon supercapacitors, hybrid supercapacitors, etc.) According to another example, the plastic ionic crystal composition or the plastic ionic crystal may be used in electrochromic materials, electrochromic cells, electrochromic devices (ECDs), and electrochromic sensors, such as those described in U.S. Patent No. 5,356,553, U.S. Patent No. 8,482,839, and U.S. Patent No. 9,249,353.

[0246] According to another example, the plastic ionic crystal composition defined herein may be a plastic ionic crystal-based solid electrolyte composition. According to another example, the plastic ionic crystal composition defined herein may be used as a component of an electrode material, for example as a binder in the electrode material.

[0247] Thus, the present technology also relates to a plastic ionic crystal-based solid electrolyte comprising a plastic ionic crystal as defined above or a plastic ionic crystal composition as defined above (i.e., comprising a plastic ionic crystal as defined above), wherein the plastic ionic crystal may be optionally crosslinked if crosslinkable functional groups are present therein.

[0248] According to one example, the plastic ionic crystalline solid electrolyte composition or the plastic ionic crystalline solid electrolyte defined above may further comprise at least one salt. For example, the salt may be dissolved in the plastic ionic crystalline solid electrolyte composition or the plastic ionic crystalline solid electrolyte.

[0249] According to another example, the salt may be an ionic salt, such as a lithium, sodium, potassium, calcium or magnesium salt. According to a variant of interest, the ionic salt is a lithium salt. Non-limiting examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide) (Li(FSI)(TFSI)), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentane). trifluoroethylsulfonyl)imide (LiBETI), lithium difluorophosphate (LiDFP), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiOTf), lithium fluoroalkylphosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate [B(C6O2)2] (LiBBB), lithium difluoro(oxalato)borate (LiBF2(C2O4)) (LiFOB), with the formula LiBF2O4R x (In the formula, R x =C 2~4According to a variant of the object, the lithium salt can be LiPF6. According to another variant of the object, the lithium salt can be LiFSI. According to another variant of the object, the lithium salt can be LiTFSI. Non-limiting examples of sodium salts include the above salts in which the lithium ions are replaced by sodium ions. Non-limiting examples of potassium salts include the above salts in which the lithium ions are replaced by potassium ions. Non-limiting examples of calcium salts include the above salts in which the lithium ions are replaced by calcium ions and the number of anions present in the salt is adjusted to the charge of the calcium ions. Non-limiting examples of magnesium salts include the above salts in which the lithium ions are replaced by magnesium ions and the number of anions present in the salt is adjusted to the charge of the magnesium ions.

[0250] According to another example, the plastic ionic crystal-based solid electrolyte composition or the plastic ionic crystal-based solid electrolyte defined above may further comprise additional components such as ion-conducting materials, inorganic particles, glass particles, ceramic particles (e.g., nanoceramics), plasticizers, and other similar components, or a combination of at least two of these. For example, the additional components may be selected for their mechanical, physical and / or chemical properties. For example, the additional components may be selected for their high ionic conductivity, and may be added to improve the conduction of lithium ions in particular. According to a variant of interest, the additional components may be selected from NASICON-type, LISICON-type, thio-LiSICON-type compounds, garnets in crystalline and / or amorphous form, and a combination of at least two of these.

[0251] According to another example, the plastic ionic crystal-based solid electrolyte may be in the form of a thin film. For example, the membrane may include at least one electrolyte layer that includes a plastic ionic crystal-based solid electrolyte. For example, additional components may be included and / or substantially dispersed in the electrolyte layer or separately in the ion conducting layer, for example, deposited on the electrolyte layer.

[0252] The present technology also relates to binder compositions comprising a plastic ionic crystal as defined herein or a plastic ionic crystal composition as defined herein together with a binder.

[0253] According to another example, the binder can be a polymer binder, for example, selected for its ability to be solubilized and effectively mixed with a solvent capable of solubilizing the plastic crystals defined herein. For example, the solvent can be an organic solvent (e.g., N-methyl-2-pyrrolidone (NMP)). The solvent can also include, for example, a polar protic solvent (e.g., isopropanol) to solubilize the polymer.

[0254] Non-limiting examples of polymer binders include ion-conducting polymer binders such as fluorine-containing polymers (e.g., polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP)), synthetic or natural rubbers (e.g., ethylene propylene diene monomer rubber (EPDM)), and copolymers composed of at least one lithium ion solvation segment, e.g., polyether, and optionally at least one crosslinkable segment (e.g., PEO-based polymers containing methyl methacrylate repeat units). According to a variant of interest, the polymer binder is a fluorine-containing polymer binder. For example, the fluorine-containing polymer binder is PTFE. Alternatively, the fluorine-containing polymer binder is PVDF or PVDF-HFP, preferably PVDF. According to another variant of interest, the polymer binder is a fluorine-free polymer binder. For example, the polymer binder is EPDM.

[0255] By way of another example, the binder can be a polymeric binder, such as the polymers described above with respect to the solid polymer electrolyte (SPE).

[0256] The present technology also relates to the use of the binder composition defined herein in an electrode material.

[0257] The present technology also relates to an electrode material comprising at least one electrochemically active material and a plastic ion crystal or a plastic ion crystal composition as defined herein. According to one example, the plastic ion crystal or the plastic ion crystal composition is a binder in the electrode material. In one example, the electrode material is a positive electrode material. In another example, the electrode material is a negative electrode material.

[0258] According to one example, the electrochemically active material may be in the form of particles. Non-limiting examples of electrochemically active materials include metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanate, metal fluorophosphates, lithium metal fluorophosphates, metal oxyfluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, lithium metal sulfates, metal halides (such as metal fluorides), lithium metal halides (such as lithium metal fluorides), sulfur, selenium, and combinations of at least two of these. According to a variant of interest, the electrochemically active material is selected from the group consisting of metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanate, lithium metal fluorides, lithium metal fluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, metal halides, sulfur, selenium, and combinations of at least two of these.

[0259] For example, the metal of the electrochemically active material, if suitable, may be selected from the group consisting of titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), chromium (Cr), copper (Cu), antimony (Sb), zirconium (Zr), zinc (Zn), niobium (Nb), and combinations of at least two thereof. By way of example of interest, the metal of the electrochemically active material, if suitable, may be selected from the group consisting of titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), zirconium (Zr), zinc (Zn), niobium (Nb), and combinations of at least two thereof. By way of further example of interest, the metal of the electrochemically active material, where suitable, may be selected from the group consisting of titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), and combinations of at least two thereof.

[0260] Non-limiting examples of electrochemically active materials include, where suitable, titanates and lithium titanates (e.g., TiO, LiTiO, LiTiO 12 , H2Ti5O 11 , H2Ti4O9, or combinations thereof), metal phosphates and lithium metal phosphates (e.g., LiM'PO4 and M'PO4, where M' can be Fe, Ni, Mn, Mg, Co, or combinations of at least two of these), vanadium oxides and vanadium metal oxides (e.g., LiVO, VO, LiVO, and other similar oxides), and other lithium metal oxides of the formula LiMn2O4, LiMO''O2, where M'' is selected from Mn, Co, Ni, and combinations thereof, or Li(NiM'')O2, where M'' is selected from Mn, Co, Al, Fe, Cr, Ti, Zr, another similar metal, and combinations thereof, and combinations of at least two of these.

[0261] According to another example, the electrochemically active material may be doped with other elements, present in small amounts as required, for example to adjust or optimize its electrochemical properties. For example, the electrochemically active material may be doped by partially replacing the metal with other ions. For example, the electrochemically active material may be doped with transition metals (e.g., Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, or Y) and / or elements other than transition metals (e.g., Mg, Al, or Sb).

[0262] According to another example, the electrochemically active material may be in the form of particles (e.g., microparticles and / or nanoparticles) that may be freshly formed or commercially sourced. For example, the electrochemically active material may be in the form of particles coated with a layer of a coating material. The coating material may be a conductive material, such as a conductive carbon coating.

[0263] According to another example, the electrode material is, for example, an anode material including carbon coated lithium titanate (C-LTO) as the electrochemically active material.

[0264] According to another example, the electrode material defined herein further comprises an additive. For example, the additive can be selected from inorganic ion-conducting materials, inorganic materials, glasses, glass-ceramics, ceramics including nanoceramics (such as Al2O3, TiO2, SiO2 and other similar compounds), salts (e.g., lithium salts) and other similar additives, or a combination of at least two of these. For example, the additive can be an inorganic ion conductor selected from NASICON-type, LISICON-type, thio-LISICON-type compounds, garnets, sulfides, sulfur halides, phosphates, thio-phosphates, and a combination of at least two of these, in crystalline and / or amorphous form.

[0265] According to another example, the electrode material defined herein further comprises a conductive material. Non-limiting examples of conductive materials include carbon sources such as carbon black (e.g., Ketjen™ carbon and Super P™ carbon), acetylene black (e.g., Shawinigan carbon and Denka™ carbon black), graphite, graphene, carbon fibers (e.g., vapor-grown carbon fibers (VGCF)), carbon nanofibers, carbon nanotubes (CNTs), and combinations of at least two of these.

[0266] By way of another example, the electrode materials defined herein may have an electrochemically active material:plastic ion crystallinity ratio of less than about 6, or less than about 5, or less than about 4, or less than about 3, preferably less than about 4.

[0267] By way of another example, the electrode materials defined herein may have a porosity of less than about 8%, or less than about 7%, or less than about 6%, or less than about 5%, or less than about 4%, or less than about 3%, or less than about 2%, or less than about 1%, preferably less than about 5%. For example, electrode performance may be limited by excessive porosity, since the pores in plastic crystal-based electrodes may act as resistance to lithium ion transport.

[0268] By way of another example, the ratio of electrochemically active material to plastic ion crystals can substantially affect the porosity of the electrode material. In some examples, to obtain substantially high electrochemical performance, an electrochemically active material:plastic ion crystal ratio of less than about 4 was used to obtain an electrode having a porosity of less than about 5%.

[0269] The present technology also relates to an electrode comprising the electrode material defined herein and applied onto a current collector (e.g., aluminum or copper foil). Alternatively, the electrode may be a self-supporting electrode. According to a variant of the object, the electrode defined herein is a positive electrode. According to another variant of the object, the electrode defined herein is a negative electrode.

[0270] Thus, the present technology also relates to a method for producing the electrode material as defined herein and the electrode as defined herein. For a more detailed understanding of the description, reference is now made to FIG. 1, which shows a flow diagram of a method for manufacturing the electrode material as defined herein, according to a possible embodiment.

[0271] As shown in FIG. 1, the method may include preparing a carbon binder slurry (CBS). The CBS preparation step includes dispersing the conductive material in a binder composition. For example, the binder composition may include a binder (e.g., the binder described above), a solvent and / or a carbon dispersant described above. As an example, the conductive material may be a combination of carbon black and VGCF, and the binder composition may include a combination of PVDF and polyvinylpyrrolidone (PVP) as the binder, and NMP as the solvent. It should be noted that PVP may also be used as a carbon dispersant. The step of dispersing the conductive material in the binder composition may be performed by any suitable method. For example, the step of dispersing the conductive material in the binder composition may be performed by a milling method, such as a ball milling method. The step of dispersing the conductive material in the binder composition may be performed for a period of time sufficient to obtain a substantially homogeneous CBS.

[0272] According to an example, preparing the CBS may also include preparing a binder composition, for example, by mixing a binder, a solvent, and / or a carbon dispersant. The preparing the binder composition may be performed by any suitable method. For example, the preparing the binder composition may be performed by a milling method, such as a roll milling method. The preparing the binder composition may be performed for a period of time sufficient to substantially dissolve the binder and / or the carbon dispersant in the solvent. For example, the preparing the binder composition may be performed for more than 10 hours.

[0273] With further reference to FIG. 1, the method may further include preparing a plastic ionic crystal (PCr)-based catholyte. For example, the PCr catholyte may be a dilute PCr catholyte. Illustratively, preparing the dilute PCr catholyte may include diluting the PCr and the ionic salt described herein (e.g., a lithium salt such as LiFSI) by adding an additional solvent to the solution. For example, the additional solvent may be NMP.

[0274] With further reference to Figure 1, the method may further include preparing a PCr-CBS slurry. For example, the step of preparing the PCr-CBS slurry may be performed by adding a diluted PCr catholyte to the CBS. For example, the diluted PCr catholyte may be added to the CBS gradually to prevent the polarity of the slurry from increasing too suddenly.

[0275] 1, the method may further include adding an electrochemically active material as described above to the PCr-CBS slurry. For example, the electrochemically active material may be lithium nickel manganese cobalt oxide (NMC).

[0276] FIG. 2 shows a flow diagram of a method for manufacturing an electrode as defined herein, according to a possible embodiment.

[0277] As shown in FIG. 2, the method may further include a step of coating the above-mentioned PCr-CBS slurry on a current collector or a substrate or support film (e.g., a substrate made of silicon, polypropylene, or siliconized polypropylene) to obtain a PCr-based positive electrode film on the current collector or support. For example, the substrate or support film may then be removed. According to a variant of the object, the PCr-CBS slurry is coated on the current collector. For example, the coating step may be performed by any suitable coating method. For example, the coating step may be performed by at least one of a doctor blade coating method, a comma coating method, a reverse comma coating method, a printing method such as gravure coating, or a slot die coating method. According to a variant of the object, the coating step is performed by a doctor blade coating method.

[0278] According to another example, the method may further include a step of drying the PCr-based positive electrode film. For example, the drying step may be performed at a temperature and for a period of time sufficient to substantially remove residual solvent. For example, the drying step may be performed in a vacuum oven at a temperature of about 120° C. for more than 10 hours to substantially remove residual solvent.

[0279] With further reference to Figure 2, the method may further include a step of calendaring or pressing the positive electrode membrane to substantially reduce its thickness. For example, the calendaring or pressing step may be performed by any suitable calendaring or pressing method. For example, the calendaring or pressing step may be performed by a roll (or between rolls) pressing method.

[0280] According to another example, the electrode material obtained by the method defined herein may be substantially or completely free of carbon aggregates compared to the electrode material obtained by the conventional mixing method. In fact, the electrode material obtained by the conventional mixing method generally contains carbon aggregates. This may be due to the fact that carbon easily aggregates in highly polar solvents due to its hydrophobic surface properties.

[0281] The present technology also relates to an electrochemical cell comprising a negative electrode, a positive electrode, and an electrolyte, wherein at least one of the negative electrode, the positive electrode, and the electrolyte comprises a plastic ionic crystal as defined herein or a plastic ionic crystal composition as defined herein.

[0282] The present technology also relates to an electrochemical cell comprising a negative electrode, a positive electrode, and an electrolyte, wherein at least one of the negative electrode, the positive electrode, and the electrolyte is as defined herein. According to a variation of the object, the electrolyte is a plastic ionic crystal solid electrolyte as defined herein. According to another variation of the object, the negative electrode is as defined herein. According to another variation of the object, the positive electrode is as defined herein. According to another variation of the object, the electrolyte is a plastic ionic crystal solid electrolyte as defined herein, and the positive electrode is as defined herein.

[0283] In some cases, the negative electrode (counter electrode) comprises an electrochemically active material that may be any known electrochemically active material and may be selected for its electrochemical compatibility with the various elements of the electrochemical cell defined herein. For example, the electrochemically active material of the negative electrode is selected for its electrochemical compatibility with the material of the positive electrode defined herein. Non-limiting examples of electrochemically active negative electrode materials include alkali metals, alkali metal alloys, graphite, silicon (Si), tin (Sn), and prelithiated electrochemically active materials. In some examples, the electrochemically active material of the negative electrode comprises lithium titanate, carbon-coated lithium titanate, an alkali metal, or an alkali metal alloy. In one variation of interest, the electrochemically active material of the negative electrode is metallic lithium.

[0284] The present technology also relates to a battery comprising at least one electrochemical cell defined herein.For example, said battery can be selected from lithium battery, lithium ion battery, lithium sulfur battery, sodium battery, sodium ion battery, magnesium battery, and magnesium ion battery.According to a variant of the object, said battery is a lithium battery or a lithium ion battery.For example, the battery can be an all-solid-state battery (e.g., an all-solid-state lithium battery). EXAMPLES

[0285] The following examples are for illustrative purposes only and should not be construed as further limiting the scope of the contemplated invention, which will be better understood with reference to the accompanying drawings.

[0286] Unless otherwise indicated, all numbers expressing amounts of ingredients, preparation conditions, concentrations, properties, and the like used herein should be understood to be modified in all cases by the term "about". At the very least, each numerical parameter should be interpreted in light of the number of reported significant digits and by applying ordinary rounding techniques. Thus, unless otherwise indicated, the numerical parameters set forth in this document are approximations that may vary depending on the desired properties. Notwithstanding the fact that the numerical ranges and parameters defining the scope of the embodiments are approximations, the numerical values ​​set forth in the following examples are reported as precisely as possible. However, any numerical values ​​inherently contain certain errors resulting from variations in experiments, testing measurements, statistical analyses, and the like.

[0287] Example 1 - Synthesis and characterization of monocationic plastic ion crystals Two methods for producing substantially pure protonic plastic ion crystals (purity about 99%) have been developed. Protonic plastic ion crystals have a glass transition temperature (T) between about -70°C and about -60°C. g) and a melting point between about 10 °C and about 45 °C. It should be noted that the melting point is decreased by the insertion of methacrylate functional groups. The reaction yield is increased in the presence of formic acid, silylated derivatives of diethylene glycol (SiDEG) and / or silylated derivatives of glycerol (SiGLY).

[0288] (a) Synthesis of silylated derivatives of diethylene glycol and glycerol The synthesis of silylated derivatives of diethylene glycol (SiDEG) and glycerol (SiGLY) was carried out by silylation of diethylene glycol or glycerol with tert-butyldimethylsilyl chloride (TBDMS-Cl) in DCM as solvent and imidazole as base and catalyst.

[0289] The silylation reaction was carried out in a glove box by adding all the reagents to a pre-cleaned and dried round-bottom flask equipped with a magnetic stirrer. The round-bottom flask was dried at a temperature of 120 °C for at least 3 h to remove residual water before the addition of the reagents.

[0290] All reagents were also pre-dried and then weighed. Diethylene glycol and glycerol were dried by azeotropic distillation with toluene and added last, i.e. after all other reagents.

[0291] The round-bottom flask was then fitted with a stopper and stirred at 1,000 rpm at room temperature for at least 15-24 hours. The mixture thus obtained was then filtered and the filtrate was further dissolved in 50 ml of DCM and washed three times with 10% (v / v) aqueous hydrochloric acid, three times with saturated aqueous sodium carbonate (Na2CO3), three times with water and finally three times with brine. The organic phase was dried for 12 hours, with stirring, over magnesium sulfate (MgSO4), used as a drying agent. The solution thus obtained was then filtered. The filtrate was evaporated to dryness and dried under vacuum for 12 hours. If an impure solution was obtained, the solution was distilled under vacuum at a temperature of 130 °C for 30 minutes to remove volatile contaminants.

[0292] The amounts, moles and equivalents of reagents used for the small scale silylation of diethylene glycol and glycerol are given in Tables 1 and 2, respectively.

[0293] [Table 1]

[0294] [Table 2]

[0295] The silylated derivatives of diethylene glycol (SiDEG) and glycerol (SiGLY) prepared in this example were analyzed by Fourier transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance ( 1 The compound was characterized by 1 H NMR.

[0296] (b) Preparation of plastic ionic crystals The synthesis was carried out in a glove box by adding all the reagents to a pre-cleaned and dried round-bottom flask equipped with a magnetic stirrer. All the reagents were also pre-dried under vacuum at a temperature below 60° C. for about 48 hours and then weighed. The round-bottom flask was dried at a temperature of 120° C. for at least 3 hours to remove residual water before the addition of the reagents.

[0297] The round bottom flask was fitted with a reflux condenser, heated to a preselected temperature and stirred at 500 rpm under an inert nitrogen atmosphere for at least 4 days. The mixture thus obtained was then cooled and the pH was measured to ensure that the mixture was under alkaline (basic) conditions. The mixture was then evaporated to dryness under vacuum at a temperature below 50° C. The residue was then dissolved in 45 ml of DCM and washed four times with water and then twice with brine. The solution thus obtained was then filtered and the filtrate was evaporated to dryness. The two phases thus formed were separated using a separatory funnel. The lower phase (yellowish phase) was collected and concentrated. The viscous solid was then distilled under vacuum at a temperature of 160° C. for about 12 hours to remove volatile contaminants. The viscous solid becomes solid at room temperature.

[0298] Plastic ion crystals (plastic crystals 1 to 14) were obtained by the method of this example. The equivalents of each reagent and the synthesis conditions are shown in Table 3, and the reaction yield and melting point of each plastic ion crystal are shown in Table 4.

[0299] [Table 3]

[0300] [Table 4]

[0301] BEMP was used as a 1 M solution of BEMP in hexane. The solvents in Table 3 are anhydrous acetonitrile (ACN), dichloromethane (DCM), dimethyl carbonate (DMC), and ethanol (EtOH).

[0302] Using the method of this example, plastic ionic crystals (plastic crystals 15 and 16) were obtained, and the amounts, moles, and equivalents of reagents used in the synthesis are shown in Tables 5 and 6, respectively.

[0303] [Table 5]

[0304] [Table 6]

[0305] FIG. 3 shows the deuterated dimethyl sulfoxide (DMSO-d 6 ) shows the proton NMR spectrum obtained for commercially available DBU in 100 ml of 10 ...

[0306] Figures 4, 5, and 6 show the carbon-13, fluorine-19, and lithium-7 nuclear magnetic resonance (NMR) spectra obtained for plastic crystal 1 in deuterated chloroform (CDCl3), respectively. 13 C NMR, 19 F NMR and 7 As shown in Figure 6, in the region from 21 ppm to -19 ppm, 7 No Li NMR peaks could be observed.

[0307] FIG. 7 shows the mass spectrum of the plastic crystal 1 obtained by high performance liquid chromatography coupled to a time-of-flight mass spectrometer equipped with an electrospray ionization source (HPLC TOF ESI-MS). - ) mode and positive (ESI + ) modes are shown.

[0308] Figure 8 shows the results of differential scanning calorimetry (DSC) analysis obtained for plastic crystal 1. Isothermal (150.00°C and -90.00°C) and non-isothermal (3.00°C / min ramp) measurements were performed. Repeated DSC heating-cooling cycle measurements were performed according to the thermal procedure: 3.00°C / min ramp from -90.00°C to 150.00°C (1), isothermal at 150.00°C for 3 minutes, 3.00°C / min ramp from 150.00°C to -90.00°C (2), isothermal at -90.00°C for 3 minutes, and 3.00°C / min ramp from -90.00°C to 150.00°C (3).

[0309] FIG. 9 shows the mass spectrum obtained by HPLC TOF ESI-MS for plastic crystal 11. The results are shown in ESI - and ESI + The following is shown.

[0310] Figure 10 shows the DSC results obtained for plastic crystal 11. Isothermal (150.00°C and -90.00°C) and non-isothermal (3.00°C / min ramp) measurements were performed. Repeated DSC heating-cooling cycle measurements were performed using the following thermal procedure: 3.00°C / min ramp from -90.00°C to 150.00°C (1), isothermal at 150.00°C for 3 minutes, 3.00°C / min ramp from 150.00°C to -90.00°C (2), isothermal at -90.00°C for 3 minutes, and 3.00°C / min ramp from -90.00°C to 150.00°C (3).

[0311] (c) Preparation of plastic ionic crystals Plastic ionic crystals were also synthesized by the following method. The synthesis was carried out in a pre-cleaned and dried round-bottom flask equipped with a magnetic stirrer in a glove box. All reagents were also pre-dried under vacuum at a temperature below 60° C. for about 48 hours and then weighed. The round-bottom flask was dried at a temperature of 120° C. for at least 3 hours to remove residual water before adding the reagents.

[0312] Using the method of this example, plastic ionic crystals (plastic crystals 17 and 18) were obtained, and the amounts, moles, and equivalents of reagents used in the synthesis are shown in Tables 7 and 8, respectively.

[0313] [Table 7]

[0314] [Table 8]

[0315] The solvent and DBU were added to the round bottom flask. The round bottom flask was then fitted with a septum, removed from the glove box and cooled to a temperature of about 4° C. Formic acid was then added dropwise to the round bottom flask with stirring. The mixture was then heated to a temperature of about 21° C. and stirred under an inert argon atmosphere for about 1 hour. The round bottom flask was fitted with a reflux condenser and stirred at 500 rpm at a temperature of 21° C. under an inert nitrogen atmosphere for at least 4 days. The mixture thus obtained was then cooled and the pH was measured to ensure that the mixture was under alkaline (basic) conditions. The mixture was then filtered and the filtrate was evaporated to dryness under vacuum at a temperature below 50° C. The residue was dissolved in 45 ml of DCM and washed four times with water and twice with brine. The two phases thus formed were separated using a separatory funnel. The lower phase (yellowish phase) was collected and concentrated. The viscous solid was then distilled under vacuum at a temperature of 160° C. for about 12 hours to remove volatile contaminants. The viscous solid becomes solid at room temperature.

[0316] (d) Post-functionalization of plastic ionic crystals prepared in Examples 1(b) and 1(c) The plastic ionic crystals prepared in Examples 1(b) and 1(c) were post-functionalized to introduce crosslinkable functional groups.

[0317] 1.50 g of the plastic ionic crystals prepared in Examples 1(b) and 1(c) were dissolved in 25 ml of anhydrous THF. 0.70 ml of 2-isocyanatoethyl methacrylate was added to the solution. The mixture thus obtained was stirred at a temperature of about 60° C. under an inert nitrogen atmosphere for about 5 hours. 5 ml of methanol was added at the end of the reaction and the mixture was cooled. The solid thus obtained was then evaporated to dryness and dried under vacuum at a temperature of about 60° C.

[0318] FIG. 11 shows the proton NMR spectrum obtained for plastic crystals 15 after post-functionalization as described in this example. 1 H NMR measurements were performed in DMSO-d 6 It was carried out inside.

[0319] Figure 12 shows the DSC results obtained for plastic crystal 15 after post-functionalization as described in this example. Isothermal (150.00°C and -90.00°C) and non-isothermal (10.00°C / min ramp) measurements were performed. Repeated DSC heating-cooling cycle measurements were performed using the following thermal procedures: 10.00°C / min ramp from -90.00°C to 150.00°C (dashed line, 1), isothermal at 150.00°C for 3 minutes (dashed line, 2), 10.00°C / min ramp from 150.00°C to -90.00°C (solid line, 3), isothermal at -90.00°C for 3 minutes (dashed line, 4), and 10.00°C / min ramp from -90.00°C to 150.00°C (dotted line, 5).

[0320] Figure 13 shows the thermogravimetric analysis (TGA) results obtained for the plastic crystals 15 after post-functionalization as described in this example. Thermal degradation of the plastic ionic crystals occurred in a programmed temperature range from room temperature to 800°C. The plastic ionic crystals were heated in an oven from room temperature to 800°C at a heating ramp rate of 10°C / min in an oxidizing environment (air).

[0321] Figure 14 shows the DSC results obtained for plastic crystal 16 after post-functionalization as described in this example. Isothermal (150.00°C and -20.00°C) and non-isothermal (2.00°C / min ramp) measurements were performed. Repeated DSC heating-cooling cycle measurements were performed using the following thermal procedures: 2.00°C / min ramp from -20.00°C to 150.00°C (dashed line, 1), isothermal at 150.00°C for 3 minutes (solid line, 2), 2.00°C / min ramp from 150.00°C to -20.00°C (dashed line, 3), isothermal at -20.00°C for 3 minutes (solid line, 4), and 2.00°C / min ramp from -20.00°C to 150.00°C (dotted line, 5).

[0322] (e) Ionic conductivity of the plastic ionic crystal shown in Example 1(d) Ionic conductivity measurements were performed by alternating current electrochemical impedance spectroscopy recorded using a VPM3 multichannel potentiostat. Electrochemical impedance spectroscopy was performed between 200 mHz and 1 MHz over a temperature range of 20 °C to 80 °C (increments and decrements of 10 °C each).

[0323] Each electrochemical impedance measurement was taken after the oven temperature was stabilized at temperature (T).

[0324] The plastic ionic crystal film is 2.01 cm 2 The electrode was placed between two stainless steel blocking electrodes having an active surface area of ​​100 nm.

[0325] The ionic conductivity of lithium ions was calculated from electrochemical impedance spectroscopy measurements using Equation 1:

number

[0326] FIG. 15 shows the temperature (K -1 ) as a function of ionic conductivity (S.cm -1 ) results. FIG. 15 shows the 1.52×10 melting point at 50° C. for plastic crystal 15 after post-functionalization as described in Example 1(d). -5 S.cm -1 It is shown that an ionic conductivity value of 0.01 was obtained.

[0327] FIG. 16 shows the temperature (K) curve for a symmetric cell assembled with plastic crystals 16 after post-functionalization as described in Example 1(d). -1 ) as a function of ionic conductivity (S.cm -1 ) results are shown.

[0328] Example 2 - Preparation of plastic ionic crystal composite membrane Ionic conductivity results were obtained for ceramic-plastic ionic crystal composite membranes containing 90 wt. % Li6PS5Cl and 10 wt. % plastic crystals 1 or 13.

[0329] Ionic conductivity results were also obtained for a ceramic-plastic ionic crystal composite membrane comprising 90 wt. % Li6PS5Cl and 10 wt. % of a plastic ionic crystal mixture comprising the polymer described in the US'674 patent (hereinafter US'674 polymer) and the plastic ionic crystals prepared in Examples 1(b)-1(d).

[0330] Finally, ionic conductivity results were obtained for a ceramic-polymer composite membrane containing 90 wt. % Li6PS5Cl and 10 wt. % US'674 polymer, as well as for a Li6PS5Cl membrane for comparison purposes.

[0331] DCM or ACN was added to the mixture as needed to obtain the appropriate viscosity. The mixture was then cast onto a pre-degreased aluminum foil. Pellets with a diameter of 10 mm were placed in a mold and compressed at a pressure of 2.8 tons using a press, then transferred to a conductivity cell at a pressure of 5 MPa. The temperature was stabilized for about 1 hour. At a temperature of 20°C, the conductivity results for the ceramic-plastic ionic crystal composite membranes ranged from about 3.0 to about 7.0 × 10 -4 S / cm range, which is similar to the conductivity results obtained for this ceramic (Li6PS5Cl) compressed without polymer or plastic ionic crystals and without aluminum support but measured under the same conditions. The conductivity results for the ceramic-plastic ionic crystal composite membrane were also significantly better than those of the ceramic-polymer composite membrane. Two impedance measurements were recorded at each temperature with 15 minutes between each measurement. The conductivity cell was assembled according to the configuration shown in Table 9.

[0332] [Table 9]

[0333] In Table 9, the term "not dried" means that the film was dried at 25°C under vacuum for 12 hours to remove only ACN. In Table 9, the term "dried" means that the film was dried at 80°C under vacuum for 12 hours to ensure sufficient drying. Thus, the plastic crystals may melt and diffuse slightly into the polymer.

[0334] FIG. 17 shows the temperature (K) curve for the conductivity cell constructed in this example. -1 ) as a function of ionic conductivity (S.cm -1 ) are shown. Results are shown for Cell 1 (●), Cell 2 (■), Cell 3 (▼), Cell 4 (★), and Cell 5 (▲) described in this example.

[0335] FIG. 18 shows the temperature (K) curve for the conductivity cell constructed in this example. -1 ) as a function of ionic conductivity (S.cm -1 ) are shown. Results are shown for Cell 6 (●), Cell 7 (▲), Cell 8 (×), Cell 9 (■), Cell 10 (◆, solid line), and Cell 11 (◆, dotted line) described in this example.

[0336] Example 4 - Anion and Cation Pairs The effect of ion pairing on the reaction yield was also determined. Plastic ionic crystals containing different combinations of cations derived from guanidine, amidine or phosphazene organic superbases and delocalized anions (plastic ionic crystals 19-28) were obtained by the method described in Example 1(b). The reaction was carried out at a temperature of about 21° C. for about 4 days.

[0337] The amounts of reagents used in the synthesis are shown in Table 10. The reaction yields and masses of the obtained plastic ion crystals are shown in Table 11.

[0338] [Table 10]

[0339] [Table 11]

[0340] Although not all results are provided, all combinations of delocalized anions with guanidine, amidine, and phosphazene organic superbases resulted in plastic ionic crystals. However, it should be understood that the pairing of anions and cations has a large effect on the mass of product obtained by the reaction and, therefore, the yield of the reaction.

[0341] Example 5 - Characterization of stabilized intermediate ion-neutral complexes As noted above, the yield of the reaction can be improved by the formation of a stabilized intermediate ion-neutral complex obtained by reacting a cation derived from a guanidine, amidine or phosphazene organic superbase described herein with a bis-silylated compound of formula 17.

[0342] The stabilized intermediate ion-neutral complex formed by the reaction of the bis-silylated derivative of diethylene glycol (SiDEG), prepared in Example 1(a), with protonated DBU was characterized.

[0343] Stabilized intermediate ion-neutral complex for approximately 3 weeks 1 H NMR and 13 It was characterized by C NMR to assess its ability to stabilize protonated bases.

[0344] FIG. 19(A) shows the atom numbering in both the protonated DBU and the bis-silylated derivative of diethylene glycol (SiDEG) prepared in Example 1(a).

[0345] FIG. 19(B) shows the proton NMR spectrum obtained for the stabilized intermediate ion-neutral complex described in this example. 1 H NMR measurements in acetonitrile-d 3( CD3CN) and peak assignments are shown in the spectra.

[0346] FIG. 19(C) shows the results obtained for the stabilized intermediate ion-neutral complexes described in this example. 13 The C NMR spectrum is shown. 13 C NMR measurements were also performed in CD3CN and peak assignments are given in the spectra.

[0347] Figure 20(A) shows the proton NMR spectra obtained for the stabilized intermediate ion-neutral complex described in this example over a three week period. 1 H NMR spectrum), after 2 days (red 1 H NMR spectrum), after 3 days (green 1 H NMR spectrum), after 9 days (purple 1 1 H NMR spectrum), and after 21 days (yellow 1 The results of H NMR spectrum are shown below. 1 1 H NMR measurements were performed in CD3CN and peak assignments are given in the spectra.

[0348] FIG. 20(B) shows the observed changes in the ion-neutral complexes over a three week period. 13 The C NMR spectrum is shown. 13 C NMR spectrum), after 2 days (red 13 C NMR spectrum), after 3 days (green 13 C NMR spectrum), after 9 days (purple 13 C NMR spectrum), and after 21 days (yellow 13 The results of the C NMR spectrum are shown below. 13 C NMR measurements were performed in CD3CN and peak assignments are given in the spectra.

[0349] As can be seen in Figures 20(A) and 20(B), no significant changes were detected in the spectra after 3 weeks, implying that there was no significant product conversion with accompanying structural changes during this period.

[0350] Figure 21(A) shows the proton NMR spectra obtained for the stabilized intermediate ion-neutral complex described in this example over a three week period. 1H NMR spectrum), after 2 days (red 1 H NMR spectrum), after 3 days (green 1 H NMR spectrum), after 9 days (purple 1 1 H NMR spectrum), and after 21 days (yellow 1 The 1 H NMR spectrum was recorded between 3.99 ppm and 4.30 ppm. 1 1 H NMR measurements were performed in CD3CN and peak assignments are given in the spectra.

[0351] Figure 21(B) shows the proton NMR spectra obtained for the stabilized intermediate ion-neutral complex described in this example over a 3-week period. Results were recorded between 6 ppm and 10.4 ppm, with the peaks at the start of the experiment (blue). 1 H NMR spectrum), after 2 days (red 1 H NMR spectrum), after 3 days (green 1 H NMR spectrum), after 9 days (purple 1 1 H NMR spectrum), and after 21 days (yellow 1 1 H NMR spectrum was obtained. 1 1 H NMR measurements were performed in CD3CN and peak assignments are given in the spectra.

[0352] The appearance of an additional minor peak (about 1% of the main compound after 21 days of reaction) can be observed at 4.16 ppm in Figure 21(A). The position of this peak and its multiplicity could potentially indicate that it corresponds to the CH2 protons of diethylene glycol without terminal silane groups.

[0353] As can be seen in FIG. 21(B), the peak corresponding to NH is significantly narrowed and shifted to higher frequencies, which is a typical behavior associated with the formation of hydrogen bonds.

[0354] Example 6 - Synthesis and characterization of polycyclic plastic ionic crystals (a) Synthesis of tetracyclic plastic ion crystal (plastic crystal 30) The synthesis of polycyclic amidines was carried out by a method similar to that described by Braddock et al. (Braddock, DC et al. "The reaction of aromatic dialdehydes with enantiopure 1,2-diamines: an expeditious route to enantiopure tricyclic amidines." Tetrahedron: Asymmetry 21.24(2010):2911-2919).

[0355] Tetracyclic plastic ion crystals (plastic crystals 30) were prepared by the method shown in Scheme 7: [ka] Scheme 7

[0356] 0.8947 g of 2,3-naphthalenedialdehyde and 60.0 ml of DCM were added to a previously cleaned and dried round bottom flask equipped with a magnetic stirrer. The solution was then stirred until dissolved. 3.30 ml of ethylenediamine was then added and the solution was stirred at a temperature of about 22° C. for about 4 hours. The solvent was then evaporated to dryness.

[0357] The synthesis was carried out in a glove box by adding all the reagents to a previously cleaned and dried round-bottom flask equipped with a magnetic stirrer. The flask was dried at a temperature of 120 °C for at least 3 h to remove residual water before adding the reagents.

[0358] A round bottom flask fitted with a reflux condenser under an inert nitrogen atmosphere was heated to a preselected temperature and stirred at 500 rpm for at least 4 days. The resulting mixture was then cooled and the pH was measured to ensure that the mixture was under alkaline (basic) conditions. The mixture was then evaporated to dryness under vacuum at a temperature below 50° C. The residue was then dissolved in 45 ml of DCM and washed four times with water and then twice with brine. The solution thus obtained was then filtered and the filtrate was evaporated to dryness. The two phases thus formed were separated using a separatory funnel. The lower phase (yellowish phase) was collected and concentrated. The viscous solid was then distilled under vacuum at a temperature of 160° C. for about 12 hours to remove volatile contaminants. The viscous solid becomes solid at room temperature.

[0359] Using the method of this example, a tetracyclic plastic ion crystal (plastic crystal 30) was obtained. The equivalents of each reagent and the synthesis conditions are shown in Table 12.

[0360] [Table 12]

[0361] (b) Characterization of tetracyclic plastic ion crystal (plastic crystal 30) FIG. 22 shows the mass spectrum obtained by HPLC TOF ESI-MS for plastic crystal 30 described in Example 6(a). - and ESI + The eluent for HPLC TOF ESI-MS was (95% methanol, 4.9% water and 0.1% formic acid) with a flow rate of 0.1 ml / min.

[0362] 23 shows the DSC results obtained for plastic crystal 30 described in Example 6(a). Isothermal (100.00° C. and −20.00° C.) and non-isothermal (2.00° C. / min ramp) measurements were performed.

[0363] Repeated DSC heating-cooling cycle measurements were performed using the following thermal procedures: 2.00° C. / min ramp from −20.00° C. to 100.00° C. (1), isothermal at 100.00° C. for 3 minutes, 2.00° C. / min ramp from 100.00° C. to −20.00° C. (2), isothermal at −20.00° C. for 3 minutes, 2.00° C. / min ramp from −20.00° C. to 100.00° C. (3), isothermal at 100.00° C. for 3 minutes, and 2.00° C. / min ramp from 100.00° C. to −20.00° C. (4). The DSC results are shown in Table 13.

[0364] [Table 13-1]

[0365] Example 7 - Synthesis and characterization of multicationic plastic ionic crystals (a) Synthesis of multicationic plastic ion crystal (plastic crystal 31) Tetracationic plastic ion crystals were prepared by the method shown in Scheme 8: [ka] Scheme 8

[0366] The synthesis of tetracationic plastic ion crystals was carried out by adding 20.0 ml of anhydrous DCM and 1.35 ml of DBU to a pre-cleaned and dried 50 ml round bottom flask equipped with a magnetic stirrer in a glove box. The mixture was then cooled to a temperature of about 4° C. outside the glove box. The mixture was then stirred and 1.0 g of 1,2,4,5-tetrakis(bromomethyl)benzene was added.

[0367] The mixture was then left under inert atmosphere at room temperature for at least 4 days. The white precipitate thus obtained was then removed by centrifugation (5000 rpm for about 10 minutes) and washed three times with 15 ml of DCM. The white solid was then dried under vacuum at a temperature of about 45° C. for 3 hours. The reaction yield was 1.624 g.

[0368] 1.624 g of the solid thus obtained, 1.71 g of LiFSI and 100 ml of absolute ethanol were added to a previously cleaned and dried 250 ml round bottom flask equipped with a magnetic stirrer in a glove box.

[0369] The mixture was then stirred at room temperature under an inert atmosphere for about 3 days. The mixture was then centrifuged and the solid was separated and collected. The solid was transferred to an 80 ml beaker and 50 ml of methanol was added. The suspension was stirred at room temperature for 15 minutes. The solid was separated and collected by centrifugation. The solid was then dried under vacuum at a temperature of about 45° C. for about 48 hours. The reaction yield was 1.62 g with a purity of 96%.

[0370] (b) Characterization of tetracationic plastic ion crystal (plastic crystal 31) 1 H and 19 Inversion recovery measurements of the longitudinal relaxation time (T1) of F nuclei were obtained for plastic crystals31.

[0371] 1.3mm MAS X / with maximum rotation speed at magic angle 67kHz 1 H / 19 NMR experiments were performed using a 500 MHz WB Bruker AVANCE NEO™ spectrometer equipped with a F NMR probe. T1 measurements were performed over the temperature range of -10 °C to 60 °C at MAS = 60 kHz. The recovery time delay was 19 F ranges from 50 microseconds to 20 seconds. 1 H was changed in 12 steps up to 50 seconds. Figures 24 and 25 show the results obtained for the tetracationic plastic ion crystal prepared in Example 7(a), respectively. 1 H NMR and 19 Figure 26 is a graph showing the relaxation time (T1) as a function of temperature for the tetracationic plastic ion crystal prepared in Example 7(a). 19 F and 1The spin-lattice relaxation rate of the H nuclei is completely described by a single exponential decay over the entire temperature range, which means that the sample is substantially homogeneous. 1 H and 19 The T1 values ​​for F are shown in Table 13.

[0372] [Table 13-2]

[0373] 1 H and 19 The T1 values ​​of F show an opposite trend with respect to temperature, which means that the cations form a "solid" type immobile framework, but the FSI anions can move in a "liquid" type manner. The tetracationic plastic ion crystal of this example was compared with plastic crystals 1 and 30. A transition from the "solid" phase to the "liquid" phase was observed at a temperature of 17°C for the anions of plastic crystal 1 and at a temperature of 40°C for the cations. The cations and anions of plastic crystal 30 were closely packed with very limited movement in the temperature range of 20°C to 60°C. Finally, the results obtained for the tetracationic plastic ion crystal of this example (plastic crystal 31) showed that in the temperature range of -10°C to 60°C, the cations form a "solid" type immobile framework, but the FSI anions can move in a "liquid" type manner.

[0374] Example 8 - Plastic Crystalline Positive Electrode (a) Preparation and characterization of plastic crystalline positive electrode films (electrodes 1 to 4) Plastic crystalline positive electrodes with different formulations and processing conditions were prepared and characterized. The electrochemically active material was lithium nickel manganese cobalt oxide (NMC). The different positive electrode compositions are shown in Table 14.

[0375] [Table 14]

[0376] Scanning electron microscope (SEM) images of electrode 1 were obtained using a TESCAN LYRA3 focused ion beam field emission scanning electron microscope (FIB-FESEM). Figure 27 shows SEM images obtained for electrode 1, showing the porosity and pore size distribution of the electrode. The cyan color in the right image represents the pores in the electrode and corresponds to most of the dark areas in the left image.

[0377] It should be noted that the pores of the plastic crystalline positive electrode can act as a resistance to lithium ion transport, and thus the positive electrode performance can be limited by the porosity. It should also be noted that the positive electrode porosity is 5% or less, and therefore the ratio of active material to plastic crystalline catholyte must be important to ensure that substantially high positive electrode performance is obtained.

[0378] Different cathode membrane compositions are shown in Table 15.

[0379] [Table 15]

[0380] (b) Preparation and characterization of plastic crystalline positive electrode film (electrode 5) A plastic crystalline positive electrode was obtained by the above method, more specifically as shown in FIG. 1 or FIG.

[0381] The CBS was prepared by adding 0.252g PVDF, 0.010g PVP, and 5.836g NMP to a container. The container and its contents were placed in a roller mill for 10 hours until dissolved. Then, 10g 3mm grinding balls, 1.260g Denka™ carbon black, and 0.42g VGCF were added to the container. The mixture was then milled in a SPEX™ mixer mill for 5 minutes, 4 times to obtain the CBS.

[0382] A diluted PCr catholyte was prepared by adding 1.934 g of plastic crystal 24, 0.120 g of LiFSI to 1.908 g of NMP, and then the solution was mixed using a vortex mixer.

[0383] A PCr-CBS solution was prepared by adding one-quarter of the diluted PCr catholyte to CBS and then grinding the mixture in a SPEX™ mixer mill for 5 minutes. This process was repeated three more times (i.e., until all of the diluted PCr catholyte had been added and mixed with CBS).

[0384] A PCr-based cathode slurry was obtained by adding 7.685 g of the PCr-CBS solution and 5.130 g of NCM 811 to the solution. The mixture was then mixed twice for 5 minutes with a vortex mixer and then three times with a homogenizer (IKA™ T-10 Basic) operated at speed level 1 for 2 minutes.

[0385] The thus obtained PCr-based positive electrode slurry was then applied onto a carbon-coated aluminum current collector using a doctor blade coating system with a fixed gap size of 150 μm.

[0386] The PCr-based positive electrode film was then dried in a vacuum oven at a temperature of 120° C. for 10 hours to remove residual solvent.

[0387] Next, the dried PCr-based positive electrode film was roll-pressed with a target thickness reduction of about 17%. The temperature setting of the roll press was adjusted so that the roll surface temperature was lower than the melting point of the plastic crystals 24.

[0388] The compositions of the PCr-CBS solution and the PCr-based positive electrode are shown in Tables 16 and 17, respectively.

[0389] [Table 16]

[0390] [Table 17]

[0391] FIG. 28 shows in (A) a photograph of the surface of a plastic crystalline positive electrode obtained by the conventional mixing method, and in (B) a photograph of the surface of a plastic crystalline positive electrode (electrode 5) obtained by the method of this example. It should be noted that these images show the direct environment reflected on the surface of the film, and this environment is not part of the electrode film. As can be seen in FIG. 28(A), the surface of the plastic crystalline positive electrode obtained by the conventional mixing method contains carbon aggregates, one example of which is circled. This can be attributed to the fact that carbon easily aggregates in highly polar solvents due to its hydrophobic surface properties. As can be seen in FIG. 28(B), the surface of the plastic crystalline positive electrode obtained by the method of this example appears substantially clear and smooth, and is substantially or completely free of carbon aggregates.

[0392] (c) Preparation and characterization of plastic crystalline positive electrode (electrode 6) and electrochemical cell (cell 12) Using the mixing method described in Example 8(b), plastic crystalline positive electrode films having the compositions shown in Table 18 were prepared.

[0393] [Table 18]

[0394] The plastic crystalline positive electrode film (electrode 6) was then coated with a ceramic-polymer composite layer. The ceramic-polymer composite layer was applied onto the plastic crystalline positive electrode film (electrode 6) using a doctor blade coating system with a fixed gap of 65 μm. The composition of the ceramic-polymer composite layer as well as its preparation method are shown in Table 19.

[0395] [Table 19]

[0396] An electrochemical cell (Cell 12) was assembled according to the configuration shown in Table 20.

[0397] [Table 20]

[0398] 29 is a graph of the discharge capacity as a function of cycle number obtained for cell 12 for 40 charge-discharge cycles. The discharge capacity was recorded at a temperature of 35° C. for the first 25 cycles, at a temperature of 50° C. for cycles 26-39, and at a temperature of 25° C. for the 40th cycle.

[0399] Example 9 - Cyclic charge and discharge (CCD) measurements CCD measurements were obtained to test the performance and cycle life for the plastic crystal compositions shown in Table 21.

[0400] [Table 21]

[0401] 30 is a graph of current density and potential as a function of time for cell 13 described in this example. Cell 7 was cycled between 3.5 V and 5.0 V in 0.1 V increments at a temperature of 50° C.

[0402] 31 is a graph of current density and potential as a function of time for cell 14 described in this example. Cell 14 was charged at 1 C, 3 mA / cm between −0.10 V and 0.10 V. 2 and a temperature of 25° C. The current density is represented by the dotted line.

[0403] 32 is a graph of current density and potential as a function of time for cells 15 and 16 described in this example. Cells 15 and 16 were charged at 1 C, 3 mA / cm between −0.15 V and 0.15 V. 2 and a temperature of 35° C. The current density is represented by the dotted line.

[0404] Example 10 - NMR diffusion studies of polymer electrolytes NMR diffusion studies of polyelectrolyte lifetimes were performed on the plastic crystal compositions shown in Table 22.

[0405] [Table 22]

[0406] Pulsed magnetic field gradient NMR diffusion measurement experiment 1 H, 7 Li, and 19 This was done for the F nucleus.

[0407] Diff50 High Power NMR Diffusion Probe and 7 Li- 19 F and 1 H- 19 NMR experiments were performed using a 500 MHz WB Bruker AVANCE NEO™ NMR spectrometer equipped with a F double-resonance radio frequency (RF) module.

[0408] Diffusion measurements were performed at a temperature of 50 °C. Gradient pulses ranged from 0.6 ms to 2.0 ms, and diffusion times ranged from 40 ms to 400 ms depending on the nucleus. Gradient strengths were varied from 100 G / cm to 2500 G / cm in 16 increments.

[0409] Diffusion measurements were performed using T2 relaxation experiments using a Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence with an echo delay between 0.06 ms and 0.6 ms. Up to 64 echoes were recorded per experiment.

[0410] The signal intensity in an NMR experiment decays exponentially after the excitation pulse:

number

[0411] Since relaxation times represent information about the local environment of the observed nuclei, they can serve as a tool for the assignment and deconvolution of NMR signals, even when their chemical shifts overlap. For example, the relaxation times of LATP 7 The transverse and longitudinal relaxation times of the Li NMR signal are reported by Arbi, K. et al. (Arbi, K. et al. Chemistry of materials 16.2 (2004): 255-262). They correspond to those observed for LATP in this example, allowing for the separation of lithium (and its diffusion coefficient) in LATP from lithium in the polymer.

[0412] The results for plastic crystals 32 and 33 are shown in Tables 23 and 24, respectively.

[0413] [Table 23]

[0414] As can be noted, the fastest proton in plastic crystal 32 was assigned to NH. The other protons could be separated into two phases (i.e., a "mobile" phase and a "stationary" phase) in a relative ratio of 2:8.

[0415] The obtained values ​​of the lithium diffusion coefficient in LATP are in a similar range to the lithium diffusion coefficient in LAGP previously reported by Hayamizu, K. et al. (Hayamizu, K. et al. Physical Chemistry Chemical Physics 19.34(2017):23483-23491).

[0416] [Table 24]

[0417] 7 Li, 19 F and 1 The diffusion coefficients of H are shown in Tables 23 and 24. For each nucleus, two particle types with different diffusivities were identified: Li in LATP and Li associated with the plastic crystal-LiTFSI mixture. + ;FSI anion and TFSI anion; the main part of the plastic crystal (CH2) and a mobile proton (NH) that can participate in hydrogen bonding.

[0418] Figure 33 shows the relationship between CH2 (▲), NH (×), FSI (◆), TFSI (●), LATP (Δ), and Li + The temperature dependence of the diffusion rate of (■) is shown as the logarithm of the diffusion coefficient (D) versus 1 / k B The Arrhenius plot of T is shown.

[0419] As can be seen in Figure 33, the Arrhenius plot corresponding to Li in LATP is linear over the entire temperature range with a diffusion activation energy of 0.26 ± 0.02 eV.

[0420] In contrast, the Arrhenius plot of the ions associated with the plastic crystal-LiTFSI mixture is linear above temperatures of about 25 °C. + , TFSI - , F.S.I. - The activation energies of , and NH are in the range of about 0.34 eV to about 0.41 eV, and the activation energy of the plastic crystal-LiTFSI mixture is about 0.50 eV. At temperatures below 25 °C, all diffusivities decrease rapidly, which can be attributed to the phase transformation of the plastic crystal.

[0421] Numerous modifications could be made to any of the above embodiments without departing from the contemplated scope of the invention. All references, patents, or scientific literature mentioned herein are incorporated by reference in their entirety for all purposes.

Claims

1. A plastic ionic crystal comprising at least one delocalized anion paired with at least one cation derived from a guanidine, amidine or phosphazene organic superbase.

2. The delocalized anion is trifluoromethanesulfonate (or triflate) [TfO] - , bis(trifluoromethanesulfonyl)imide [TFSI] - , bis(fluorosulfonyl)imide [FSI] - , 2-trifluoromethyl-4,5-dicyanoimidazolate [TDI] - , hexafluorophosphate [PF 6 ] - , and tetrafluoroborate [BF 4 ] - 2. The plastic ionic crystal of claim 1, wherein the delocalized anion is selected from the group consisting of: [TFSI] − or [FSI] − .

3. The cation is a cation derived from a guanidine, amidine or phosphazene organic superbase of formula 2-8: 【Chemistry 28】 (In the formula, The plastic ion crystal is a monocationic plastic ion crystal, R 1 is a hydrogen atom or C 1 ~C 10 Alkyl-acrylate, C 1 ~C 10 Alkyl-methacrylate, carbonylamino-C 1 ~C 10 Alkyl-methacrylate, carbonylamino-C 1 ~C 10 Alkyl-acrylate, carbonyloxy-C 1 ~C 10 Alkyl-methacrylate, and carbonyloxy-C 1 ~C 10 R 1 is a linear or branched substituent selected from alkyl-acrylates, preferably R 1 is a hydrogen atom and said plastic ionic crystal is a protic plastic ionic crystal, or R 1 is a linear or branched substituent selected from C 1 -C 10 alkyl-acrylates, C 1 -C 10 alkyl-methacrylates, carbonylamino-C 1 -C 10 alkyl-methacrylates, and carbonylamino-C 1 -C 10 alkyl-acrylates and said plastic ionic crystal is a crosslinked plastic ionic crystal; or The plastic ionic crystal is a multicationic plastic ionic crystal comprising at least two delocalized anions paired with at least two cations derived from a guanidine, amidine or phosphazene organic superbase, R 1 is an optionally substituted organic bridging group separating at least two of said cations, and may be linear or branched C 1 ~C 10 Alkylene, linear or branched C 1 ~C 10 Alkyleneoxy C 1 ~C 10 Alkylene, linear or branched poly(C 1 ~C 10 Alkyleneoxy)C 1 ~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C 6 ~C 12 Arylene, C 5 ~C 12 Heteroarylene, C 3 ~C 12 Cycloalkylene, and C 3 ~C 12 heterocycloalkylene).

3. The plastic ionic crystal according to claim 1 or 2, selected from the group consisting of:

4. The plastic ionic crystal is a plastic ionic crystal of formulas 10-16: 【Chemical 29】 【Chemistry 30】 (In the formula, X - is [TfO] - , [TFSI] - , [FSI] - , [TDI] - , [PF 6 ] - , and [BF 4 ] - wherein the delocalized anion is selected from the group consisting of [TFSI] − and [FSI] − anions, preferably the delocalized anion is selected from the group consisting of [TFSI] − and [FSI] − anions, more preferably the delocalized anion is [FSI] − ; The plastic ion crystal is a monocationic plastic ion crystal, R 1 is a hydrogen atom or C 1 ~C 10 Alkyl-acrylate, C 1 ~C 10 Alkyl-methacrylate, carbonylamino-C 1 ~C 10 Alkyl-methacrylate, carbonylamino-C 1 ~C 10 Alkyl-acrylate, carbonyloxy-C 1 ~C 10 Alkyl-methacrylate, and carbonyloxy-C 1 ~C 10 R 1 is a linear or branched substituent selected from alkyl-acrylates, preferably R 1 is a hydrogen atom and said plastic ionic crystal is a protic plastic ionic crystal, or R 1 is a linear or branched substituent selected from C 1 -C 10 alkyl-acrylates, C 1 -C 10 alkyl-methacrylates, carbonylamino-C 1 -C 10 alkyl-methacrylates, and carbonylamino-C 1 -C 10 alkyl-acrylates and said plastic ionic crystal is a crosslinked plastic ionic crystal; or The plastic ionic crystal is a multicationic plastic ionic crystal comprising at least two delocalized anions paired with at least two cations derived from a guanidine, amidine or phosphazene organic superbase, R 1 is an optionally substituted organic bridging group separating at least two of said cations, and may be linear or branched C 1 ~C 10 Alkylene, linear or branched C 1 ~C 10 Alkyleneoxy C 1 ~C 10 Alkylene, linear or branched poly(C 1 ~C 10 Alkyleneoxy)C 1 ~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C 6 ~C 12 Arylene, C 5 ~C 12 Heteroarylene, C 3 ~C 12 Cycloalkylene, and C 3 ~C 12 heterocycloalkylene).

4. The plastic ionic crystal of claim 3, selected from:

5. A plastic ionic crystal composition comprising at least one plastic ionic crystal as defined in any one of claims 1 to 4 and at least one additional component and / or at least one polymer.

6. The additional component is preferably an inorganic particle comprising a compound having a garnet, NASICON-type, LISICON-type, thio-LISICON-type, LIPON-type, perovskite-type, antiperovskite-type or argyrodite-type structure or a compound of the M-P-S-type, M-P-S-O-type, M-P-S-X-type, M-P-S-O-X-type, in a crystalline, amorphous and / or glass-ceramic phase, or a mixture of at least two of these, where M is an alkali metal or an alkaline earth metal and X is F, Cl, Br, I or a combination of at least two of these, and preferably the inorganic particle comprises the following compound in a crystalline, amorphous, glass-ceramic phase or a combination thereof: -MLZO (e.g., M 7 La 3 Zr 2 O 12 , M (7-a) La 3 Zr 2 Al b O 12 , M (7-a) La 3 Zr 2 Ga b O 12 , M (7-a) La 3 Zr (2-b) Ta b O 12 and M (7-a) La 3 Zr (2-b) Nb b O 12 ); -MLTaO (e.g., M 7 La 3 Ta 2 O 12 , M 5 La 3 Ta 2 O 12 and M 6 La 3 Ta 1.5 Y 0.5 O 12 ); -MLSnO (e.g., M 7 La 3 Sn 2 O 12 ). -MAGP (e.g., M 1+a A a Ge 2-a (P.O. 4 ) 3 ). -MAPP (e.g., M 1+a A a Ti 2-a (P.O. 4 ) 3 ). -MLTiO (e.g., M 3a La (2/3-a) TiO 3 ). -MZP (e.g., M a Zr b (P.O. 4 ) c ). -MCZP (e.g., M a Ca b Zr c (P.O. 4 ) d ). - MGPS (e.g. M 10 GeP 2 S 12 M such as a Ge b P c S d ). - MGPSO (e.g. M a Ge b P c S d O e ). -MSiPS (e.g., M 10 SiP 2 S 12 M such as a S b P c S d ). -MSiPSO (e.g., M a S b P c S d O e ). -MSnPS (e.g., M 10 SnP 2 S 12 M such as a Sn b P c S d ). -MSnPSO (e.g., M a Sn b P c S d O e ). - MPS (e.g., M 7 P 3 S 11 M such as a P b S c ). -MPSO (e.g., M a P b S c O d ). -MZPS (e.g., M a Zinc b P c S d ). -MZPSO (e.g., M a Zinc b P c S d O e ). -xM 2 S-yP 2 S 5 ; -xM 2 S-yP 2 S 5 -zMX; -xM 2 S-yP 2 S 5 -zP 2 O 5 ; -xM 2 S-yP 2 S 5 -zP 2 O 5 -wMX; -xM 2 S-yM 2 O-zP 2 S 5 ; -xM 2 S-yM 2 O-zP 2 S 5 -wMX; -xM 2 S-yM 2 O-zP 2 S 5 -wP 2 O 5 ; -xM 2 S-yM 2 O-zP 2 S 5 -wP 2 O 5 -vMX; -xM 2 S-ySiS 2 ; -MPSX (e.g., M 7 P 3 S 11 X, M 7 P 2 S 8 X and M 6 P.S. 5 M such as X a P b S c X d ). -MPSOX (e.g., M a P b S c O d X e ). - MGPSX (e.g. M a Ge b P c S d X e ). -MGPSOX (e.g., M a Ge b P c S d O e X f ). -MSiPSX (e.g., M a S b P c S d X e ). -MSiPSOX (e.g., M a S b P c S d O e X f ). -MSnPSX (e.g., M a Sn b P c S d X e ). - MSnPSOX (e.g., M a Sn b P c S d O e X f ). -MZPSX (e.g., M a Zinc b P c S d X e ). -MZPSOX (e.g., M a Zinc b P c S d O e X f ). -M 3 OX; -M 2 HOX; -M 3 PO 4 ; -M 3 P.S. 4 and -M a PO b N c (a=2b+3c-5) (In the formula, M is an alkali metal ion, an alkaline earth metal ion, or a combination thereof, and when M comprises an alkaline earth metal ion, the number of M's is adjusted to achieve electroneutrality; X is selected from F, Cl, Br, I, or combinations thereof; a, b, c, d, e and f are numbers other than 0 and are independently selected in each formula to achieve electroneutrality; v, w, x, y and z are numbers other than 0 and are independently selected in each formula to provide a stable compound. At least one of More preferably, the inorganic particles are Li 10 GeP 2 S 12 , Li 6 P.S. 5 Cl, Li 2 S-P 2 S 5 , Li 7 P 3 S 11 , Li 9.54 S 1.74 P 1.44 S 11.7 C 0.3 , Li 9.6 P 3 S 12 , and Li 3.25 P 0.95 S 4 6. The plastic ionic crystal composition of claim 5, wherein the sulfide-based ceramic is selected from the group consisting of:

7. The polymer is linear or branched; It is bridged, a polyether type polymer, preferably a polyethylene oxide (PEO) based polymer, or 32. A block copolymer comprising at least one lithium ion solvating segment and optionally at least one crosslinkable segment, said lithium ion solvating segment comprising a repeating unit of formula 32: 【Chemistry 31】 (In the formula, R 3 is a hydrogen atom, C 1 ~C 10 Alkyl group or -(CH 2 -O-R 4 R 5 ) group; R 4 (CH 2 -CH 2 -O) m and R 5 is a hydrogen atom and C 1 ~C 10 alkyl groups; y is an integer selected from the range of 10 to 200,000; m is an integer selected from the range of 0 to 10. and wherein the polymer is selected from a homopolymer or copolymer having the formula:

7. The plastic ionic crystal composition of claim 5 or 6, wherein the crosslinkable segment of the copolymer is a block copolymer, preferably a polymer segment comprising at least one functional group that is multidimensionally crosslinkable by irradiation or heat treatment.

8. The plastic ionic crystal composition is (i) A plastic ionic crystal-based electrolyte composition; (ii) contained in a binder; (iii) contained in an electrochemical cell; (iv) in a supercapacitor, preferably a carbon-carbon supercapacitor; or (v) A plastic ionic crystal composition according to any one of claims 5 to 7, which is contained in an electrochromic material.

9. A solid electrolyte composition comprising a plastic ionic crystal as defined in any one of claims 1 to 4 or a plastic ionic crystal composition as defined in any one of claims 5 to 7, and at least one salt or at least one additional component.

10. The salt is an ionic salt, preferably selected from lithium, sodium, potassium, calcium and magnesium salts, more preferably the ionic salt is a lithium salt, preferably lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide) (Li(FSI)(TFSI)), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium difluorophosphate (LiDFP), lithium tetrafluoroborate (LiBF 4 ), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO 3 ), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO 4 ), lithium hexafluoroarsenate (LiAsF 6 ), lithium trifluoromethanesulfonate (LiSO 3 CF 3 ) (LiOTf), lithium fluoroalkyl phosphate Li[PF 3 (CF 2 CF 3 ) 3 ] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF 3 ) 4 ](LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O′)borate Li[B(C 6 O 2 ) 2 ] (LiBBB), lithium difluoro(oxalato)borate (LiBF 2 (C 2 O 4 )) (LiFOB), formula LiBF 2 O 4 R x (In the formula, R x = C 2~4 alkyl), and combinations of at least two thereof; or 10. The solid electrolyte composition of claim 9, wherein the additional component is selected from the group consisting of ion-conducting materials, inorganic particles, glass particles, ceramic particles, plasticizers, other like components, and combinations of at least two thereof, or selected from crystalline and / or amorphous forms of NASICON-type, LISICON-type, thio-LiSICON-type compounds, garnets, and combinations of at least two thereof.

11. A solid electrolyte comprising a plastic ionic crystal as defined in any one of claims 1 to 4, or a solid electrolyte composition as defined in claim 9 or 10, wherein the solid electrolyte is optionally crosslinked.

12. (i) an electrode material comprising an electrochemically active material and a plastic ionic crystal as defined in any one of claims 1 to 4, said plastic ionic crystal being optionally crosslinked and / or a binder; or (ii) An electrode material comprising an electrochemically active material and a plastic ionic crystal composition as defined in any one of claims 5 to 7, said plastic ionic crystal composition being optionally crosslinked and / or being a binder.

13. 13. The electrode material of claim 12, wherein the electrochemically active material is in the form of particles and / or is selected from the group consisting of metal oxides, lithium metal oxides, metal phosphates, lithium metal phosphates, titanates, lithium titanate, metal fluorophosphates, lithium metal fluorophosphates, metal oxyfluorophosphates, lithium metal oxyfluorophosphates, metal sulfates, lithium metal sulfates, metal halides (e.g., metal fluorides), lithium metal halides (e.g., lithium metal fluorides), sulfur, selenium, and combinations of at least two thereof, the metal being preferably selected from the group consisting of titanium (Ti), iron (Fe), magnesium (Mg), manganese (Mn), vanadium (V), nickel (Ni), cobalt (Co), aluminum (Al), zirconium (Zr), zinc (Zn), niobium (Nb), and combinations of at least two thereof.

14. 14. The electrode material according to claim 12 or 13, wherein the electrode material further comprises at least one conductive material, preferably the conductive material is selected from carbon black, acetylene black, graphite, graphene, carbon fibers, carbon nanofibers, carbon nanotubes, and a combination of at least two thereof.

15. 15. An electrode comprising an electrode material as defined in any one of claims 12 to 14 on a current collector.

16. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, (i) at least one of the negative electrode, the positive electrode, and the electrolyte comprises at least one plastic ionic crystal as defined in any one of claims 1 to 4, the plastic ionic crystal being optionally crosslinked; or (ii) at least one of the negative electrode, the positive electrode, and the electrolyte comprises a plastic ionic crystal composition as defined in any one of claims 5 to 7, the plastic ionic crystal composition being optionally crosslinked; or (iii) at least one of the negative electrode and the positive electrode is as defined in claim 15; or (iv) An electrochemical cell, wherein the electrolyte is a solid electrolyte as defined in claim 11.

17. 17. An electrochemical accumulator comprising at least one electrochemical cell as defined in claim 16, said electrochemical accumulator being preferably a battery selected from lithium batteries, lithium ion batteries, sodium batteries, sodium ion batteries, magnesium batteries and magnesium ion batteries, more preferably a lithium battery or a lithium ion battery.

18. A method for preparing a plastic ionic crystal as defined in any one of claims 1 to 4 or a plastic ionic crystal composition as defined in any one of claims 5 to 7, said method comprising the steps of: (i) reacting at least one guanidine, amidine or phosphazene organic superbase with at least one proton source to form at least one complex comprising a cation derived from a protonated guanidine, amidine or phosphazene organic superbase and a counterion; and (ii) reacting said complex comprising a cation and a counterion derived from a protonated guanidine, amidine or phosphazene organic superbase with at least one ionic salt, preferably said ionic salt being an alkali or alkaline earth metal salt selected from lithium, sodium, potassium, calcium or magnesium salts, more preferably a lithium salt.

19. Steps (i) and (ii) are carried out sequentially, simultaneously or partially overlapping with one another; the guanidine, amidine or phosphazene organic superbase, the proton source and the ionic salt are mixed together and allowed to react; steps (i) and (ii) are carried out in the presence of a solvent, and optionally said solvent is said proton source for step (i); said proton source of step (i) is a first proton source, and steps (i) and (ii) are carried out in the presence of a second proton source; wherein steps (i) and (ii) are carried out in the presence of an activator and / or stabilizer, and the method further comprises the step of forming a stabilized intermediate ion-neutral complex; steps (i) and (ii) are carried out at a temperature in the range of about 20° C. to about 200° C., inclusive; and / or 20. The method of claim 18, wherein steps (i) and (ii) are carried out for at least 4 days.

20. The activator and / or stabilizer is a bis-silylated compound of formula 17: 【Chemistry 32】 (In the formula, Z is a straight or branched C 1 ~C 10 Alkylene, linear or branched C 1 ~C 10 Alkyleneoxy C 1 ~C 10 Alkylene, linear or branched poly(C 1 ~C 10 Alkyleneoxy)C 1 ~C 10 a substituted or unsubstituted organic group selected from alkylene, linear or branched polyethers, linear or branched polycarbonates, linear or branched polythiocarbonates, linear or branched polyamides, linear or branched polyimides, linear or branched polyurethanes, linear or branched polysiloxanes, linear or branched thioethers, linear or branched polyphosphazenes, linear or branched polyesters, and linear or branched polythioesters; R 2 is independently, at each occurrence, selected from the group consisting of alkyl groups, aryl groups, and arylalkyl groups. and 20. The method of claim 19, wherein said method optionally further comprises the step of preparing said bis-silylated compound of formula 17, preferably said step being carried out by a silylation reaction of a compound containing at least two hydroxyl groups with a silylation reagent.

21. The method comprises at least one of the following steps: a purification step, preferably carried out by extraction, distillation or evaporation; A functionalization step is preferably carried out by reaction between the -NH functional group of the protonated guanidine, amidine or phosphazene organic superbase derived cation and at least one precursor of a crosslinkable functional group, the crosslinkable functional group being preferably a precursor of C 1 ~C 10 Alkyl-acrylate, C 1 ~C 10 Alkyl-methacrylate, carbonyloxy-C 1 ~C 10 Alkyl-methacrylate, carbonyloxy-C 1 ~C 10 Alkyl-acrylate, carbonylamino-C 1 ~C 10 Alkyl-methacrylate, and carbonylamino-C 1 ~C 10 a functionalization step, A step of coating the plastic ionic crystal composition or a suspension containing the plastic ionic crystals on a substrate; drying the composition or suspension; and a crosslinking step, which is preferably carried out by UV irradiation, by heat treatment, by microwave irradiation, under electron beam, by gamma irradiation or by X-ray irradiation, 21. The method of any one of claims 18 to 20, further comprising:

22. A method for preparing a plastic ionic crystal as defined in any one of claims 1 to 4 or a plastic ionic crystal composition as defined in any one of claims 5 to 7, comprising the steps of: (i) reacting a guanidine, amidine or phosphazene organic superbase with an organic bridging compound to form a multicationic complex comprising at least two organic superbase cationic moieties separated by an optionally substituted organic bridging group and paired with a counterion; and (ii) reacting said multicationic complex with at least one ionic salt, preferably said ionic salt being an alkali or alkaline earth metal salt selected from lithium, sodium, potassium, calcium or magnesium salts, more preferably a lithium salt. The method includes:

23. said organic bridging compound comprises said optionally substituted organic bridging group and at least two anionic leaving groups, preferably said anionic leaving groups are halides selected from F - , Cl - , Br - , and I - , more preferably Br -; The optionally substituted organic bridging group is a linear or branched C 1 ~C 10 Alkylene, linear or branched C 1 ~C 10 Alkyleneoxy C 1 ~C 10 Alkylene, linear or branched poly(C 1 ~C 10 Alkyleneoxy)C 1 ~C 10 Alkylene, linear or branched polyether, linear or branched polyester, C 6 ~C 12 Arylene, C 5 ~C 12 Heteroarylene, C 3 ~C 12 Cycloalkylene, and C 3 ~C 12 Heterocycloalkylenes, the organic bridging group is 1,2,4,5-tetrakis(bromomethyl)benzene; Steps (i) and (ii) are carried out sequentially, simultaneously or partially overlapping with one another; the guanidine, amidine or phosphazene organic superbase, the organic cross-linking compound and the ionic salt are mixed together and allowed to react; Steps (i) and (ii) are carried out in the presence of a solvent; the step of reacting the guanidine, amidine or phosphazene organic superbase with the organic cross-linking compound is carried out in the presence of a base; Steps (i) and (ii) are carried out at room temperature; and / or, the step of reacting the guanidine, amidine or phosphazene organic superbase with the organic cross-linking compound is carried out for about 4 days; and / or 23. The method of claim 22, wherein the step of reacting the multicationic complex with the ionic salt is carried out for about 3 days.

24. The method of claim 23, further comprising at least one of the following steps: A purification step, preferably carried out by extraction, distillation or evaporation, and coating said plastic ionic crystal composition or a suspension containing said plastic ionic crystals onto a substrate, and optionally drying said composition or suspension.

24. The method of claim 22 or 23, further comprising:

25. A method for producing an electrode material as defined in any one of claims 12 to 14, said method comprising the following steps: (i) preparing a carbon and binder slurry; (ii) preparing a plastic ionic crystal-based catholyte; and (iii) preparing a plastic ionic crystal, carbon and binder slurry; The method includes:

26. 26. The method of claim 25, wherein the step of preparing a carbon and binder slurry comprises dispersing the carbon in a binder composition, the binder composition comprising a binder and optionally a solvent and / or a carbon dispersant.

27. 27. The method of claim 26, wherein the method further comprises the step of preparing the binder composition, preferably said step being carried out by mixing the binder with the solvent and / or the carbon dispersant.

28. the step of preparing the plastic ionic crystal catholyte comprises diluting the plastic ionic crystals and an ionic salt in a solvent; the step of preparing the plastic ionic crystal, carbon and binder slurry comprises stepwise addition of the plastic ionic crystal catholyte to the carbon and binder slurry; and / or 28. The method of any one of claims 25 to 27, wherein the method further comprises the step of adding an electrochemically active material to the plastic ionic crystal, carbon, and binder slurry.

29. 29. The method of any one of claims 25 to 28, wherein the method further comprises coating the plastic ionic crystal, carbon, and binder slurry onto a current collector to obtain a plastic ionic crystal, carbon, and binder electrode film on a current collector.

30. The method comprises at least one of the following steps: drying the plastic ionic crystals, binder, and carbon electrode film; and calendering the plastic ionic crystals, binder, and carbon electrode film; 30. The method of claim 29, further comprising: